Solid ion conductor and method for producing the same, solid electrolyte, and electrochemical device
Patent Information
- Application Number
- CN202110900394.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-06
- Filing Date
- 2021-08-06
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-08-06
Smart Images

Figure CN114069029B_ABST
Abstract
Description
[0001] Cross-reference to related applications
[0002] This application claims priority to Korean Patent Application No. 10-2020-0098821, filed on August 6, 2020, with the Korean Intellectual Property Office, the entire contents of which are incorporated herein by reference. Technical Field
[0003] This disclosure relates to solid ionic conductors, solid electrolytes including said solid ionic conductors, lithium batteries including said solid electrolytes, and methods for preparing said ionic conductors. Background Technology
[0004] All-solid-state secondary batteries can provide improved stability by using a solid electrolyte instead of a liquid electrolyte, and can provide improved energy density by using lithium metal as the negative electrode active material.
[0005] Solid electrolytes are electrochemically stable within the charge-discharge voltage range of secondary batteries and conduct lithium ions at room temperature.
[0006] Due to the need for all-solid-state secondary batteries with improved performance, there is a continuous demand for solid electrolytes that possess excellent physical properties in addition to superior ionic conductivity. Summary of the Invention
[0007] A novel composition of solid ionic conductors with reduced interfacial resistance is provided.
[0008] A solid electrolyte comprising the solid ionic conductor is provided.
[0009] An electrochemical device comprising the solid ionic conductor is provided.
[0010] A method for preparing the solid ionic conductor is provided.
[0011] Other aspects will be set forth in part in the description which follows, and will also be apparent in part from the description, or may be learned by practice of the embodiments of this disclosure presented.
[0012] According to one embodiment, the solid ionic conductor comprises: a garnet-type oxide represented by Formula 1:
[0013] Formula 1
[0014] Li A M1 B La C M2 D Zr E M3 F M4 G OH X I
[0015] Wherein, in the above Formula 1,
[0016] M1 is a monovalent cation, a divalent cation, a trivalent cation, or a combination thereof,
[0017] M2 is a monovalent cation, a divalent cation, a trivalent cation, or a combination thereof,
[0018] M3 is a divalent cation, a trivalent cation, a tetravalent cation, a pentavalent cation, a hexavalent cation, or a combination thereof,
[0019] M4 is Ir, Ru, Mn, Sn, or a combination thereof,
[0020] X is a monovalent anion, a divalent anion, a trivalent anion, or a combination thereof, and
[0021] 6≤A≤8, 0≤B<2, 2.8≤C≤3, 0≤D≤0.2, 0<E<2.0, 0<F<2.0, 0<G≤0.2, 9≤H≤12, and 0≤I≤2.
[0022] In an aspect of another embodiment, a solid electrolyte includes the solid ionic conductor.
[0023] In an aspect of another embodiment, an electrochemical device includes: a positive electrode; a negative electrode; and a solid electrolyte layer disposed between the positive electrode and the negative electrode, wherein the positive electrode, the negative electrode, the solid electrolyte layer, or a combination thereof includes the solid ionic conductor.
[0024] In another embodiment, an electrochemical device includes: a positive electrode; a negative electrode; a solid electrolyte layer disposed between the positive electrode and the negative electrode; and a positive electrode protective layer on the positive electrode, a negative electrode protective layer on the negative electrode, a solid electrolyte protective layer on the solid electrolyte, or a combination thereof, wherein the positive electrode protective layer, the negative electrode protective layer, the solid electrolyte protective layer, or a combination thereof includes the solid ionic conductor.
[0025] In an aspect of another embodiment, a method of preparing a solid ionic conductor includes: providing a precursor mixture comprising precursors for forming the solid ionic conductor; and
[0026] subjecting the precursor mixture to heat treatment in an oxidizing atmosphere to provide the solid ionic conductor including a garnet-type oxide represented by Formula 1.
[0027] A method of manufacturing an electrochemical device includes: providing a positive electrode; providing a negative electrode; and disposing a solid electrolyte layer between the positive electrode and the negative electrode to manufacture the electrochemical device, wherein the positive electrode, the negative electrode, the solid electrolyte layer, or a combination thereof comprises the solid ion conductor. Attached Figure Description
[0028] The above and other aspects, features, and advantages of some embodiments of this disclosure will become clearer from the following description taken in conjunction with the accompanying drawings, wherein:
[0029] Figure 1 The graph shows the intensity (arbitrary unit, au) versus diffraction angle (degrees, 2θ) and displays the results of powder X-ray diffraction analysis of the solid ionic conductors prepared in Examples 1, 2 and Comparative Example 1.
[0030] Figure 2 A graph of conductivity (σ, Siemens / cm, S / cm) versus temperature (1000 / T, 1 / Kelvin, 1 / K) is shown, along with the results of Arrhenius analysis of the solid ionic conductors prepared in Examples 1 and 2.
[0031] Figure 3A The graph shows the intensity (arbitrary unit, au) versus Raman shift (1 / cm, 1 / cm) and displays the Raman spectrum of the solid ionic conductor prepared in Example 1;
[0032] Figure 3B The graph shows the intensity (arbitrary unit, au) versus Raman shift (1 / cm, 1 / cm) and also displays the Raman spectrum of the solid ionic conductor prepared in Comparative Example 1.
[0033] Figure 4 Voltage (V) versus capacity (mAh / cm²) 2 A graph showing the charge-discharge curves of the all-solid-state secondary battery manufactured in Example 9, along with its capacity (mAh / g).
[0034] Figure 5 A cross-sectional view of one embodiment of an all-solid-state secondary battery;
[0035] Figure 6 A cross-sectional view of another embodiment of an all-solid-state secondary battery; and
[0036] Figure 7 This is a cross-sectional view of another embodiment of an all-solid-state secondary battery. Detailed Implementation
[0037] The embodiments will now be described in detail, examples of which are shown in the accompanying drawings, wherein the same reference numerals always refer to the same elements. In this respect, the embodiments may take different forms and should not be construed as limited to the description set forth herein. Therefore, the embodiments are described below only by reference to the accompanying drawings to illustrate aspects. As used herein, the term "and / or" includes any and all combinations of one or more of the associated enumerated items. Expressions such as "at least one of" modify the entire list of elements when preceding or following it, without modifying any individual element of the list.
[0038] Various embodiments are illustrated in the accompanying drawings. However, the inventive concept can be embodied in many different forms and should not be construed as limited to the embodiments described herein. Rather, these embodiments are provided so that this disclosure is sufficient and complete, and fully conveys the scope of the inventive step to those skilled in the art. The same reference numerals denote the same components.
[0039] When a component is mentioned as being placed "on" another component, it is understood that it may be directly on the other component or that an intermediate element may be present between them. Conversely, when a component is mentioned as being "directly on" another component, there is no intermediate element.
[0040] Although the terms "first," "second," "third," etc., may be used herein to describe various elements, components (assemblies), regions, and / or layers, these elements, components (assemblies), regions, and / or layers should not be limited by these terms. These terms are used only to distinguish one element, component (assembly), region, or layer from another. Therefore, without departing from the teachings of this specification, the first component (assembly), first element, first region, first layer, or first area described below may be referred to as a second component (assembly), second element, second region, second layer, or second area.
[0041] The terminology used in this specification is for descriptive purposes only and is not intended to limit the inventive step of the invention. As used herein, the singular form is intended to include the plural form, including "at least one," unless explicitly stated otherwise. "At least one" should not be construed as limited to the singular form. As used herein, the term "and / or" includes any and all combinations of one or more of the listed items. It will be further understood that the terms "comprising" and / or "including," when used in this specification, indicate the presence of the stated features, integrals, steps, operations, elements, and / or components (assemblies), but do not preclude the presence or addition of one or more additional features, integrals, steps, operations, elements, components (assemblies), and / or collections thereof.
[0042] Spatially relative terms such as “below,” “under,” “below,” “above,” “over,” and “on top” are used herein to readily describe the relationship of one component or feature to another. It will be understood that, in addition to the orientations shown in the figures, spatially relative terms are also intended to include different orientations of the device in use or operation. For example, if the device in the figure is flipped, the component described as “below” or “under” another component or feature will be oriented “above” said other component or feature. Thus, the exemplary term “below” can include both upward and downward orientations. The device may be positioned in different orientations (rotated 90 degrees or rotated in other orientations), and the spatially relative terms used herein may be interpreted accordingly.
[0043] As used herein, “about” or “approximately” includes the stated value and means within an acceptable range of deviations from the specific value, as determined by a person skilled in the art taking into account the measurement in question and the errors associated with the measurement of the specific quantity (i.e., limitations of the measurement system). For example, “about” may mean within one or more standard deviations relative to the stated value, or within ±30%, 20%, 10%, or 5%.
[0044] Unless otherwise defined, all terms used in this specification (including technical and scientific terms) shall have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure pertains. Furthermore, it is understood that terms defined in common dictionaries shall be interpreted as having meanings consistent with their meanings in the context of the relevant art and within this disclosure, and shall not be interpreted as idealized or overly formal.
[0045] Embodiments are described herein with reference to cross-sectional views, which are schematic diagrams of idealized embodiments. Thus, deviations from the shape of the component should be anticipated as a result of, for example, manufacturing techniques and / or tolerances. Therefore, the embodiments described herein should not be construed as limited to the specific shapes of the regions shown herein, but should include deviations in shape caused, for example, by manufacturing processes. For example, regions illustrated or described as flat may typically have rough and / or non-linear characteristics. Furthermore, sharp corners illustrated may be rounded. Therefore, the regions shown in the figures are schematic in nature, and their shapes are not intended to show the precise shapes of the regions, nor are they intended to limit the scope of the claims.
[0046] The term "group" refers to a group of elements in the periodic table according to the International Union of Pure and Applied Chemistry ("IUPAC") Group 1-18 classification system.
[0047] Although specific embodiments have been described, alternatives, modifications, variations, improvements, and substantial equivalents that are presently unexpected or unforeseen may occur to the applicant or those skilled in the art. Accordingly, it is intended that the appended claims, as they may be filed and amended, cover all such alternatives, modifications, variations, improvements, and substantial equivalents.
[0048] Hereinafter, the solid ion conductor according to the embodiment, a solid electrolyte including the solid ion conductor, an electrochemical cell including the solid ion conductor, and a method of preparing the solid ion conductor will be described in more detail.
[0049] Solid ion conductor
[0050] The solid ion conductor according to the embodiment includes a garnet-type oxide represented by Formula 1:
[0051] Formula 1
[0052] Li A M1 B La C M2 D Zr E M3 F M4 G O H X I
[0053] wherein, in Formula 1,
[0054] M1 is a monovalent cation, a divalent cation, a trivalent cation, or a combination thereof,
[0055] M2 is a monovalent cation, a divalent cation, a trivalent cation, or a combination thereof,
[0056] M3 is a divalent cation, a trivalent cation, a tetravalent cation, a pentavalent cation, a hexavalent cation, or a combination thereof,
[0057] M4 is Ir, Ru, Mn, Sn, or a combination thereof,
[0058] X is a monovalent anion, a divalent anion, a trivalent anion, or a combination thereof, and satisfies 6≤A≤8, 0≤B<2, 2.8≤C≤3, 0≤D≤0.2, 0<E<2.0, 0<F<2.0, 0<G≤0.2, 9≤H≤12, and 0≤I≤2.
[0059] Solid ionic conductors, as described herein, possess an electrochemically stable voltage window and excellent ionic conductivity within the driving voltage range of a secondary battery. Conventional solid ionic conductors generally include elements whose oxidation numbers remain unchanged within the driving voltage range of the secondary battery and do not include electrochemically active elements, such as those that are oxidized or reduced within the driving voltage range. In conventional solid ionic conductors that include electrochemically stable elements, the charge transfer reaction rate decreases at their surface. For example, conventional solid ionic conductors exhibit high interfacial resistance at the interface with lithium metal. Therefore, secondary batteries including such solid ionic conductors have increased internal resistance and degraded charge-discharge characteristics.
[0060] Conversely, since solid ionic conductors comprising garnet-type oxides represented by Formula 1 contain electrochemically active elements such as Ir, Ru, Mn, or Sn within a certain content range of the driving voltage range of the secondary battery, their charge transfer reaction rate is increased compared to that of conventional solid ionic conductors. Therefore, solid ionic conductors comprising garnet-type oxides represented by Formula 1, in addition to excellent lithium-ion conductivity, also exhibit reduced interfacial resistance with lithium metal. As a result, the reversibility of electrode reactions in secondary batteries containing solid ionic conductors comprising garnet-type oxides represented by Formula 1 is improved. Without being bound by theory, it is considered that when the content of electrochemically active elements in the garnet-type oxide represented by Formula 1 is greater than the content defined in Formula 1, side reactions on the surface of the solid ionic conductor may increase, and therefore its interfacial resistance may increase.
[0061] In Equation 1, M3 can be a cation of an element other than Ir, Ru, Mn and Sn.
[0062] Garnet is a silicate that can be represented by the formula A3X2(SiO4)3, where A is a divalent cation and X is a trivalent cation. As used herein, the terms “garnet” or “garnet-like” refer to compounds isomorphous to garnet, such as Mg3Al2(SiO4)3, and may have cubic symmetry.
[0063] In Formula 1, for example, 6≤A≤7.9, 6≤A≤7.8, 6≤A≤7.5, 6≤A≤7.2, or 6≤A≤7 is satisfied. In Formula 1, for example, 2.8≤C≤3, 2.85≤C≤3, 2.9≤C≤3, or 2.95≤C≤3 is satisfied. In Formula 1, for example, 0<E≤1.9, 0<E≤1.8, 0<E≤1.7, 0<E≤1.6, or 0<E≤1.5 is satisfied. In Formula 1, for example, 0<F≤1.0, 0<F≤0.9, 0<F≤0.8, 0<F≤0.7, 0<F≤0.6, or 0<F≤0.5 is satisfied. In Formula 1, for example, 0.001<G≤0.2, 0.01<G≤0.2, 0<G≤0.19, 0<G≤0.18, or 0<G≤0.17 is satisfied.
[0064] In Formula 1, examples of the monovalent cation may include Na, K, Rb, Cs, H, or Fr, and examples of the divalent cation may include Mg, Ca, Ba, or Sr. Examples of the trivalent cation may include In, Sc, Cr, Au, B, Al, or Ga, and examples of the tetravalent cation may include Sn, Ti, Mn, Ir, Ru, Pd, Mo, Hf, Ge, V, or Si. Examples of the pentavalent cation may include Nb, Ta, Sb, V, and P. Examples of the hexavalent cation may include Cr, Mo, or W.
[0065] In the solid ion conductor, for example, the garnet-type oxide represented by Formula 1 may be a garnet-type oxide represented by Formula 2:
[0066] Formula 2
[0067] Li A M1 B (La a1 M2 a2 )3(Zr b1 M3 b2 M4 b3 )2O H X I
[0068] wherein, in Formula 2,
[0069] M1 is a monovalent cation, a divalent cation, a trivalent cation, or a combination thereof,
[0070] M2 is a monovalent cation, a divalent cation, a trivalent cation, or a combination thereof,
[0071] M3 is a divalent cation, a trivalent cation, a tetravalent cation, a pentavalent cation, a hexavalent cation, or a combination thereof,
[0072] M4 is Ir, Ru, Mn, Sn, or a combination thereof,
[0073] X is a monovalent anion, a divalent anion, a trivalent anion, or a combination thereof,
[0074] satisfies 6≤A≤8, 0≤B<2, 9≤H≤12, and 0≤I≤2, and
[0075] satisfies a1+a2=1, 0<a1≤1, 0≤a2≤0.067, b1+b2+b3=1, 0<b1<1, 0<b2<1, and 0<b3≤0.1.
[0076] In Formula 2, for example, it satisfies 0<b1≤0.95, 0<b1≤0.9, 0<b1≤0.85, 0<b1≤0.8, or 0<b1≤0.75. In Formula 2, for example, it satisfies 0<b2≤0.5, 0<b2≤0.45, 0<b2≤0.4, 0<b2≤0.35, 0<b2≤0.3, or 0<b2≤0.25. In Formula 2, for example, it satisfies 0<b3≤0.095, 0<b1≤0.090, 0<b1≤0.085, 0<b1≤0.080, or 0<b1≤0.075.
[0077] In the solid ionic conductor, for example, the garnet-type oxide represented by Formula 1 may be a garnet-type oxide represented by Formula 3:
[0078] Formula 3
[0079] Li A M1 B (La a1 M2 a2 )3(Zr b1 M5 b4 M6 b5 M7 b6 M8 b7 )2O H X I
[0080] wherein, in Formula 3,
[0081] M1 is a monovalent cation, a divalent cation, a trivalent cation, or a combination thereof,
[0082] M2 is a monovalent cation, a divalent cation, a trivalent cation, or a combination thereof,
[0083] M5, M6, and M7 are each independently a divalent cation, a trivalent cation, a tetravalent cation, a pentavalent cation, a hexavalent cation, or a combination thereof,
[0084] M8 is Ir, Ru, Mn, Sn, or a combination thereof,
[0085] X is a monovalent anion, divalent anion, trivalent anion, or a combination thereof,
[0086] satisfies 6≤A≤8, 0≤B<2, 9≤H≤12, and 0≤I≤2, and
[0087] satisfies a1+a2=1, 0<a1≤1, 0≤a2≤0.067, b1+b4+b5+b6+b7=1, 0<b1<1, 0<b4<1, 0<b5<1, 0≤b6<1, and 0<b7≤0.1.
[0088] In Formula 3, for example, it satisfies 0<b1≤0.95, 0<b1≤0.90, 0<b1≤0.85, 0<b1≤0.80, 0<b1≤0.75, 0<b1≤0.6, 0<b1≤0.5, 0<b1≤0.45, 0<b1≤0.4, 0<b1≤0.35, 0<b1≤0.3, or 0<b1≤0.25. In Formula 3, for example, it satisfies 0<b4≤0.5, 0<b4≤0.45, 0<b4≤0.4, 0<b4≤0.35, 0<b4≤0.3, or 0<b4≤0.25. In Formula 3, for example, it satisfies 0<b5≤0.5, 0<b5≤0.45, 0<b5≤0.4, 0<b5≤0.35, 0<b5≤0.3, or 0<b5≤0.25. In Formula 3, for example, it satisfies 0<b5≤0.5, 0<b5≤0.45, 0<b5≤0.4, 0<b5≤0.35, 0<b5≤0.3, or 0<b5≤0.25. In Formula 3, for example, it satisfies 0<b7≤0.095, 0<b7≤0.090, 0<b7≤0.085, 0<b7≤0.080, or 0<b7≤0.075.
[0089] Since the garnet-type oxide contains five or more elements including Zr, M5, M6, M7, and M8, or four elements including Zr, M5, M6, and M8 at specific sites in its crystal structure, the configurational entropy of the substituted crystalline phase can be increased to stabilize the crystalline phase, thereby increasing the ionic conductivity of the oxide and improving the lithium reduction stability of the oxide. Such a crystalline phase may be, for example, a cubic phase.
[0090] In Formula 3, the five or more elements including Zr, M5, M6, M7, and M8, or the four elements including Zr, M5, M6, and M8 may have the following combinations:
[0091] Four tetravalent cations (Combination 1);
[0092] A combination of two tetravalent cations, one trivalent cation and one pentavalent cation (Combination 2);
[0093] A combination of two tetravalent cations, one divalent cation, and one hexavalent cation (combination 3);
[0094] A combination of three tetravalent cations, one trivalent cation, and one pentavalent cation (combination 4);
[0095] A combination of three tetravalent cations, one divalent cation, and one hexavalent cation (combination 5);
[0096] Combinations of two tetravalent cations, one trivalent cation, and two pentavalent cations (combination 6);
[0097] A combination of four tetravalent cations, one trivalent cation, and one pentavalent cation (combination 7);
[0098] A combination of four tetravalent cations, one divalent cation, and one hexavalent cation (combination 8);
[0099] Combinations of two tetravalent cations, two trivalent cations, and two pentavalent cations (combination 9);
[0100] A combination of two tetravalent cations, two divalent cations, and two hexavalent cations (combination 10); or
[0101] Five tetravalent cations (combination 11).
[0102] Combination 1 is, for example, Zr / Hf / Sn / Ru, Zr / Hf / Sn / Mo, Zr / Hf / Sn / Ir, Zr / Hf / Sn / Pd, Zr / Hf / Ru / Ir, Zr / Hf / Ru / Mo, Zr / Hf / Ru / Pd, Zr / Hf / Ir / Mo, Zr / Hf / Ir / Pd, Zr / Hf / Mo / Mn, or a combination thereof. Combination 2 is, for example, Zr / Ir / In / Nb, Zr / Ir / In / Ta, Zr / Ir / In / Sb, Zr / Ir / Sc / Nb, Zr / Ir / Sc / Ta, Zr / Ir / Sc / Sb, Zr / Ir / Cr / Nb, Zr / Ir / Cr / Ta, Zr / Ir / Cr / Sb, Zr / Ru / In / Nb, Zr / Ru / In / Ta, Zr / Ru / In / Sb, Zr / Ru / Sc / Nb, Zr / Ru / Sc / Ta, Zr / Ru / Sc / Sb, Zr / Ru / Cr / Nb, Zr / Ru / Cr / Ta, Zr / Ru / Cr / Sb, Zr / Sn / In / Nb, Zr / Sn / In / Ta, Zr / Sn / In / Sb, Zr / Sn / Sc / Nb, Zr / Sn / Sc / Ta, Zr / Sn / Sc / Sb, Zr / Sn / Cr / Nb, Zr / Sn / Cr / Ta, Zr / Sn / Cr / Sb, or a combination thereof. Combination 3 is, for example, Zr / Ir / Ni / Ru, Zr / Ir / Ni / Mo, Zr / Ir / Cu / Ru, Zr / Ir / Cu / Mo, Zr / Ir / Mg / Ru, Zr / Ir / Mg / Mo, Zr / Mn / Ni / Ru, Zr / Mn / Ni / Mo, Zr / Mn / Cu / Ru, Zr / Mn / Cu / Mo, Zr / Mn / Mg / Ru, Zr / Mn / Mg / Mo, Zr / Sn / Ni / Ru, Zr / Sn / Ni / Mo, Zr / Sn / Cu / Ru, Zr / Sn / Cu / Mo, Zr / Sn / Mg / Ru, Zr / Sn / Mg / Mo, or a combination thereof.Combination 4 is, for example, Zr / Hf / Sn / In / Nb, Zr / Hf / Sn / In / Ta, Zr / Hf / Sn / In / Sb, Zr / Hf / Sn / Sc / Nb, Zr / Hf / Sn / Sc / Ta, Zr / Hf / Sn / Sc / Sb, Zr / Hf / Sn / Cr / Nb, Zr / Hf / Sn / Cr / Ta, Zr / Hf / Sn / Cr / Sb, Zr / Hf / Ru / In / Nb, Zr / Hf / Ru / In / Ta, Zr / Hf / Ru / In / Sb, Zr / Hf / Ru / Sc / Nb, Zr / Hf / Ru / Sc / Ta, Zr / Hf / Ru / Sc / Sb, Zr / Hf / Ru / Cr / Nb, Zr / Hf / Ru / Cr / Ta, Zr / Hf / Ru / Cr / Sb, Zr / Mo / Sn / In / Nb, Zr / Mo / Sn / In / Ta, Zr / Mo / Sn / In / Sb, Zr / Mo / Sn / Sc / Nb, Zr / Mo / Sn / Sc / Ta, Zr / Mo / Sn / Sc / Sb, Zr / Mo / Sn / Cr / Nb, Zr / Mo / Sn / Cr / Ta, Zr / Mo / Sn / Cr / Sb, or a combination thereof. Combination 5 is, for example, Zr / Hf / Sn / Ni / Ru, Zr / Hf / Sn / Ni / Mo, Zr / Hf / Sn / Cu / Ru, Zr / Hf / Sn / Cu / Mo, Zr / Hf / Sn / Mg / Ru, Zr / Hf / Sn / Mg / Mo, Zr / Hf / Ir / Ni / Ru, Zr / Hf / Ir / Ni / Mo, Zr / Hf / Ir / Cu / Ru, Zr / Hf / Ir / Cu / Mo, Zr / Hf / Ir / Mg / Ru, Zr / Hf / Ir / Mg / Mo, or a combination thereof.Combination 6 is, for example, Zr / Ir / Sc / Nb / Ta, Zr / Ir / Sc / Nb / Sb, Zr / Ir / Sc / Ta / Sb, Zr / Ir / Cr / Nb / Ta, Zr / Ir / Cr / Nb / Sb, Zr / Ir / Cr / Ta / Sb, Zr / Ir / In / Nb / Ta, Zr / Ir / In / Nb / Sb, Zr / Ir / In / Ta / Sb, Zr / Ru / In / Nb / Ta, Zr / Sn / In / Nb / Sb, Zr / Sn / In / Ta / Sb, Zr / Ru / Cr / Nb / Ta, Zr / Ru / Cr / Nb / Sb, Zr / Ru / Cr / Ta / Sb, Zr / Ru / Sc / Nb / Ta, Zr / Mn / Sc / Nb / Sb, Zr / Mn / Sc / Ta / Sb, Zr / Sn / In / Nb / Ta, Zr / Sn / In / Nb / Sb, Zr / Sn / In / Ta / Sb, Zr / Sn / Cr / Nb / Ta, Zr / Sn / Cr / Nb / Sb, Zr / Sn / Cr / Ta / Sb, Zr / Sn / Sc / Nb / Ta, Zr / Sn / Sc / Nb / Sb, Zr / Sn / Sc / Ta / Sb, or a combination thereof. Combination 7 is, for example, Zr / Hf / Sn / Ru / In / Nb, Zr / Hf / Sn / Ru / In / Ta, Zr / Hf / Sn / Ru / In / Sb, Zr / Hf / Sn / Ru / Sc / Nb, Zr / Hf / Sn / Ru / Sc / Ta, Zr / Hf / Sn / Ru / Sc / Sb, Zr / Hf / Sn / Ru / Cr / Nb, Zr / Hf / Sn / Ru / Cr / Ta, Zr / Hf / Sn / Ru / Cr / Sb, Zr / Hf / Sn / Mo / In / Nb, Zr / Hf / Sn / Mo / In / Ta, Zr / Hf / Sn / Mo / In / Sb, Zr / Hf / Sn / Mo / Sc / Nb, Zr / Hf / Sn / Mo / Sc / Ta, Zr / Hf / Sn / Mo / Sc / Sb, Zr / Hf / Sn / Mo / Cr / Nb, Zr / Hf / Sn / Mo / Cr / Ta, Zr / Hf / Sn / Mo / Cr / Sb, or a combination thereof. Combination 8 is, for example, Zr / Hf / Sn / Mn / Ni / Ru, Zr / Hf / Sn / Mn / Ni / Mo, Zr / Hf / Sn / Mn / Cu / Ru, Zr / Hf / Sn / Mn / Cu / Mo, Zr / Hf / Sn / Mn / Mg / Ru, Zr / Hf / Sn / Mn / Mg / Mo, Zr / Hf / Sn / Pd / Ni / Ru, Zr / Hf / Sn / Pd / Ni / Mo, Zr / Hf / Sn / Pd / Cu / Ru, Zr / Hf / Sn / Pd / Cu / Mo, Zr / Hf / Sn / Pd / Mg / Ru, Zr / Hf / Sn / Pd / Mg / Mo, or a combination thereof.Combination 9 is, for example, Zr / Ir / In / Sc / Nb / Ta, Zr / Ir / In / Sc / Nb / Sb, Zr / Ir / In / Sc / Ta / Sb, Zr / Ir / In / Cr / Nb / Ta, Zr / Ir / In / Cr / Nb / Sb, Zr / Ir / In / Cr / Ta / Sb, Zr / Ir / Cr / Sc / Nb / Ta, Zr / Ir / Cr / Sc / Nb / Sb, Zr / Ir / Cr / Sc / Ta / Sb, or combinations thereof. Combination 10 is, for example, Zr / Ir / Cu / Ni / Ru / Mo, Zr / Sn / Cu / Ni / Ru / Mo, Zr / Mn / Cu / Ni / Ru / Mo, Zr / Ir / Mg / Ni / Ru / Mo, Zr / Sn / Mg / Ni / Ru / Mo, Zr / Mn / Mg / Ni / Ru / Mo, Zr / Ir / Ca / Ni / Ru / Mo, Zr / Mn / Ca / Ni / Ru / Mo, Zr / Sn / Ca / Ni / Ru / Mo, or combinations thereof. Combination 11 is, for example, Zr / Hf / Sc / Ta / Ru, Zr / Hf / Sc / Ta / Mn, Zr / Hf / Sc / Ta / Ir, Zr / Hf / Sc / Ta / Sn, Zr / Hf / Cr / Ta / Ru, Zr / Hf / Sc / Ta / Mn, Zr / Hf / Sc / Ta / Ir, Zr / Hf / Sc / Ta / Sn, or combinations thereof.
[0103] In the case of four elements, the molar ratio of the four elements can be 4:4:4:0.1~1.1, 3:5:3:0.1~1.1, 5:3:5:0.1~1.1, 3:5:4:0.1~1.1, or 5:3:4:0.1~1.1. In the case of five elements, the molar ratio of the five elements can be 5:5:5:5:0.1~1.1, 4:6:4:6:0.1~1.1, 6:4:6:4:0.1~1.1, 4:4:6:6:0.1~1.1, 6:6:4:4:0.1~1.1, 3:3:7:7:0.1~1.1, 7:7:3:3:0.1~1.1, 8:2:8:2:0.1~1.1, 7:3:7:3:0.1~1.1, 8:8:2:2:0.1~1.1, or 2:2:8:8:0.1~1.1. In the case of six elements, the molar ratio of the six elements can be 4:4:4:4:4:0.1~1.1, 3:5:3:5:4:0.1~1.1, 5:3:5:3:4:0.1~1.1, 3:5:4:3:5:0.1~1.1, or 5:3:4:5:3:0.1~1.1.
[0104] In the solid ionic conductor, for example, the garnet-type oxide represented by Formula 1 can be a garnet-type oxide represented by Formula 4:
[0105] Formula 4
[0106] Li 7-w M1 x La 3-y M2 y Zr 2-z-u M3 z M4 u O 12-v X v
[0107] wherein, in Formula 4,
[0108] M1 is H, Fe, Ga, Al, B, Be, or a combination thereof,
[0109] M2 is Ba, Ca, Sr, Y, Bi, Pr, Nd, Ac, Sm, Gd, or a combination thereof,
[0110] M3 is Al, Ga, Ta, Nb, Hf, Ti, V, Cr, Co, Ni, Cu, Mo, W, Mg, Tc, Ru, Pd, Sc, Cd, In, Sb, Te, Tl, Pt, Si, or a combination thereof,
[0111] M4 is Ir, Ru, Mn, Sn, or a combination thereof,
[0112] X is a monovalent anion, a divalent anion, a trivalent anion, or a combination thereof,
[0113] 0≤x≤2, 0≤y≤0.2, 0<z<2, 0<u≤0.2, 0<v<2, 0<z+u<2 are satisfied, and w=[a×x]+[(b-3)×y]+[(c-4)×z]+[(d-4)×u]+[(e+2)×v], as well as
[0114] a is the oxidation number of M1, b is the oxidation number of M2, c is the oxidation number of M3, d is the oxidation number of M4, and e is the oxidation number of X. In Formula 4, z is, for example, greater than 0 and 1.5 or less, greater than 0 and 1.0 or less, or greater than 0 and 0.5 or less. z is, for example, 0.5. In Formula 4, u is, for example, greater than 0 and 0.2 or less, greater than 0 and 0.18 or less, greater than 0 and 0.15 or less, greater than 0 and 0.12 or less, greater than 0 and 0.10 or less, greater than 0 and 0.08 or less, or greater than 0 and 0.05 or less. In Formula 4, for example, 0<z+u<1.5, 0<z+u<1.0, 0<z+u<0.8, 0<z+u<0.6, 0<z+u<0.5, or 0<z+u<0.4 is satisfied.
[0115] In the solid ion conductor, for example, the garnet-type oxide represented by Formula 1 may be a garnet-type oxide represented by Formula 5:
[0116] Formula 5
[0117] Li 7-w M1 x La 3-y M2 y Zr 2-p-q-r-s M5 p M6 q M7 r M8 s O 12-v X v
[0118] wherein, in Formula 5,
[0119] M1 is H, Fe, Ga, Al, B, Be, or a combination thereof,
[0120] M2 is Ba, Ca, Sr, Y, Bi, Pr, Nd, Ac, Sm, Gd, or a combination thereof,
[0121] M5, M6, and M7 are each independently Al, Ga, Ta, Nb, Hf, Ti, V, Cr, Co, Ni, Cu, Mo, W, Mg, Tc, Ru, Pd, Sc, Cd, In, Sb, Te, Tl, Pt, Si, or a combination thereof,
[0122] M8 is Ir, Ru, Mn, Sn, or a combination thereof,
[0123] X is a monovalent anion, a divalent anion, a trivalent anion, or a combination thereof,
[0124] satisfying 0≤x≤2, 0≤y≤0.2, 0<p<2, 0<q<2, 0≤r<2, 0<s≤0.2, 0<v<2, 0<p+q+r+s<2, and w=[a×x]+[(b-3)×y]+[(f-4)×p]+[(g-4)×q]+[(h-4)×r]+[(i-4)×s]+[(e+2)×v], as well as
[0125] a is the oxidation number of M1, b is the oxidation number of M2, f is the oxidation number of M5, g is the oxidation number of M6, h is the oxidation number of M7, i is the oxidation number of M8, and e is the oxidation number of X.
[0126] In Formula 5, p, q, and r are each independently, for example, greater than 0 and 1.0 or less, greater than 0 and 0.9 or less, greater than 0 and 0.8 or less, greater than 0 and 0.7 or less, greater than 0 and 0.6 or less, greater than 0 and 0.5 or less, greater than 0 and 0.4 or less, greater than 0 and 0.3 or less, or greater than 0 and 0.2 or less. p is, for example, 0.4-0.5. In Formula 5, s is, for example, greater than 0 and 0.2 or less, greater than 0 and 0.18 or less, greater than 0 and 0.15 or less, greater than 0 and 0.12 or less, greater than 0 and 0.10 or less, greater than 0 and 0.08 or less, or greater than 0 and 0.05 or less. In Formula 5, for example, 0<p+q+r+s<1.9, 0<p+q+r+s<1.8, 0<p+q+r+s<1.7, 0<p+q+r+s<1.6, 0<p+q+r+s<1.5, 0<p+q+r+s<1.0, or 0<p+q+r+s<0.5 is satisfied.
[0127] In the solid ion conductor, for example, in Formulas 1 to 5, X may be iodine (I), chlorine (Cl), bromine (Br), fluorine (F), cyanide, cyanate, thiocyanate, azide (N₃ - ), or a combination thereof. In Formulas 1 to 5, for example, X may be I, Cl, Br, or F. In Formulas 1 to 5, for example, X may be F.
[0128] In the solid ion conductor, for example, the garnet-type oxide represented by Formula 1 may be a garnet-type oxide represented by Formula 6:
[0129] Formula 6
[0130] Li 7-w La₃Zr 2-z-u M9 z M10 u O 12
[0131] wherein, in Formula 6,
[0132] M9 is Al, Ga, Ta, Nb, Hf, Ti, V, Cr, Co, Ni, Cu, Mo, W, Mg, Tc, Ru, Pd, Sc, Cd, In, Sb, Te, Tl, Pt, Si, or a combination thereof,
[0133] M10 is Ir, Ru, Mn, Sn, or a combination thereof,
[0134] c is the oxidation number of M9, d is the oxidation number of M10, and 0<z<2, 0<u≤0.2, 0<z+u<2, and w=[(c-4)×z]+[(d-4)×u] are satisfied. In Formula 6, for example, M9 can be Al, Ga, Ta, Nb, or a combination thereof, and M10 can be Ir, Ru, or a combination thereof. In Formula 6, z is, for example, greater than 0 and 1.5 or less, greater than 0 and 1.0 or less, or greater than 0 and 0.5 or less. In Formula 6, u is, for example, greater than 0 and 0.2 or less, greater than 0 and 0.18 or less, greater than 0 and 0.15 or less, greater than 0 and 0.12 or less, greater than 0 and 0.10 or less, greater than 0 and 0.08 or less, or greater than 0 and 0.05 or less. In Formula 6, for example, 0<z+u<1.5, 0<z+u<1.0, 0<z+u<0.8, 0<z+u<0.6, 0<z+u<0.5, or 0<z+u<0.4 is satisfied.
[0135] In the solid ion conductor, for example, the garnet-type oxide represented by Formula 1 can be a garnet-type oxide represented by Formula 7:
[0136] Formula 7
[0137] Li 7-w La3Zr 2-p-q-r-s M11 p M12 q M13 r M14 s O 12
[0138] wherein, in Formula 7,
[0139] M11, M12, and M13 are each independently Al, Ga, Ta, Nb, Hf, Ti, V, Cr, Co, Ni, Cu, Mo, W, Mg, Tc, Ru, Pd, Sc, Cd, In, Sb, Te, Tl, Pt, Si, or a combination thereof,
[0140] M14 is Ir, Ru, Mn, Sn, or a combination thereof,
[0141] f is the oxidation number of M11, g is the oxidation number of M12, h is the oxidation number of M13, and i is the oxidation number of M14, and 0<p<2, 0<q<2, 0≤r<2, 0<s≤0.2, 0<p+q+r+s<2, and w=[(f-4)×p]+[(g-4)×q]+[(h-4)×r]+[(i-4)×s] are satisfied. In Formula 7, for example, M11 is Al, Ga, Ta, Nb, or a combination thereof, M12 and M13 are each independently Hf, Sc, In, or a combination thereof, and M14 is Ir, Ru, Sn, or a combination thereof. In Formula 7, p, q, and r are each independently, for example, greater than 0 and 1.0 or less, greater than 0 and 0.9 or less, greater than 0 and 0.8 or less, greater than 0 and 0.7 or less, greater than 0 and 0.6 or less, greater than 0 and 0.5 or less, greater than 0 and 0.4 or less, greater than 0 and 0.3 or less, or greater than 0 and 0.2 or less. In Formula 7, s is, for example, greater than 0 and 0.2 or less, greater than 0 and 0.18 or less, greater than 0 and 0.15 or less, greater than 0 and 0.12 or less, greater than 0 and 0.10 or less, greater than 0 and 0.08 or less, or greater than 0 and 0.05 or less. In Formula 7, for example, 0<p+q+r+s<1.9, 0<p+q+r+s<1.8, 0<p+q+r+s<1.7, 0<p+q+r+s<1.6, 0<p+q+r+s<1.5, 0<p+q+r+s<1.0, or 0<p+q+r+s<0.5 is satisfied.
[0142] In the solid ion conductor, for example, the garnet-type oxide represented by Formula 1 may be a garnet-type oxide represented by any one of the following formulas:
[0143] Li 7-w La3Zr 2-z-u Al z Ir u O 12 (6≤7-w≤8, 0<z≤1, 0<u≤0.2), Li 7-w La3Zr 2-z-u Al z Ru u O 12 (6≤7-w≤8, 0<z≤1, 0<u≤0.2), Li 7-w La3Zr 2-z-u Al z Mn u O 12 (6≤7-w≤8, 0<z≤1, 0<u≤0.2), Li 7-w La3Zr 2-z-u Al z Sn u O12 (6≤7-w≤8, 0) <z≤1,0<u≤0.2);
[0144] Li 7-w La3Zr 2-z-u Ga z Ir u O 12 (6≤7-w≤8, 0) <z≤1,0<u≤0.2),Li 7-w La3Zr 2-z-u Ga z Ru u O 12 (6≤7-w≤8, 0) <z≤1,0<u≤0.2),Li 7-w La3Zr 2-z-u Ga z Mn u O 12 (6≤7-w≤8, 0) <z≤1,0<u≤0.2),Li 7-w La3Zr 2-z-u Ga z Sn u O 12 (6≤7-w≤8, 0) <z≤1,0<u≤0.2);
[0145] Li 7-w La3Zr 2-z-u Ta z Ir u O 12 (6≤7-w≤8, 0) <z≤1,0<u≤0.2),Li 7-w La3Zr 2-z-u Ta z Ru u O 12 (6≤7-w≤8, 0) <z≤1,0<u≤0.2),Li 7-w La3Zr 2-z-u Ta z Mn u O 12 (6≤7-w≤8, 0) <z≤1,0<u≤0.2),Li 7-w La3Zr 2-z-u Ta z Sn u O 12 (6≤7-w≤8, 0) <z≤1,0<u≤0.2);
[0146] Li 7-w La3Zr 2-z-u Nb z Ir u O 12(6≤7-w≤8, 0) <z≤1,0<u≤0.2),Li 7-w La3Zr 2-z-u Nb z Ru u O 12 (6≤7-w≤8, 0) <z≤1,0<u≤0.2),Li 7-w La3Zr 2-z-u Nb z Mn u O 12 (6≤7-w≤8, 0) <z≤1,0<u≤0.2),Li 7-w La3Zr 2-z-u Nb z Sn u O 12 (6≤7-w≤8, 0) <z≤1,0<u≤0.2);
[0147] Li 7-w La3Zr 2-p-q-r-s Al p Hf q Sc r Ir s O 12 (6≤7-w≤8, 0) <p≤1,0<q≤1,0<r≤1,0<s≤0.2,0<p+q+r+s<2),Li 7-w La3Zr 2-p-q-r-s Al p Hf q Sc r Ru s O 12 (6≤7-w≤8, 0) <p≤1,0<q≤1,0<r≤1,0<s≤0.2,0<p+q+r+s<2),Li 7-w La3Zr 2-p-q-r-s Al p Hf q Sc r Mn s O 12 (6≤7-w≤8, 0) <p≤1,0<q≤1,0<r≤1,0<s≤0.2,0<p+q+r+s<2),Li 7-w La3Zr 2-p-q-r-s Al p Hf q Sc r Sn s O 12 (6≤7-w≤8, 0) <p≤1,0<q≤1,0<r≤1,0<s≤0.2,0<p+q+r+s<2);
[0148] Li7-w La3Zr 2-p-q-r-s Ga p Hf q Sc r Ir s O 12 (6≤7-w≤8, 0) <p≤1,0<q≤1,0<r≤1,0<s≤0.2,0<p+q+r+s<2),Li 7-w La3Zr 2-p-q-r-s Ga p Hf q Sc r Ru s O 12 (6≤7-w≤8, 0) <p≤1,0<q≤1,0<r≤1,0<s≤0.2,0<p+q+r+s<2),Li 7-w La3Zr 2-p-q-r-s Ga p Hf q Sc r Mn s O 12 (6≤7-w≤8, 0) <p≤1,0<q≤1,0<r≤1,0<s≤0.2,0<p+q+r+s<2),Li 7-w La3Zr 2-p-q-r-s Ga p Hf q Sc r Sn s O 12 (6≤7-w≤8, 0) <p≤1,0<q≤1,0<r≤1,0<s≤0.2,0<p+q+r+s<2);
[0149] Li 7-w La3Zr 2-p-q-r-s Ta p Hf q Sc r Ir s O 12 (6≤7-w≤8, 0) <p≤1,0<q≤1,0<r≤1,0<s≤0.2,0<p+q+r+s<2),Li 7-w La3Zr 2-p-q-r-s Ta p Hf q Sc r Ru s O 12 (6≤7-w≤8, 0) <p≤1,0<q≤1,0<r≤1,0<s≤0.2,0<p+q+r+s<2),Li 7-w La3Zr 2-p-q-r-s Ta pHf q Sc r Mn s O 12 (6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, 0<p+q+r+s<2), Li 7-w La3Zr 2-p-q-r-s Ta p Hf q Sc r Sn s O 12 (6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, 0<p+q+r+s<2);
[0150] Li 7-w La3Zr 2-p-q-r-s Nb p Hf q Sc r Ir s O 12 (6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, 0<p+q+r+s<2), Li 7-w La3Zr 2-p-q-r-s Nb p Hf q Sc r Ru s O 12 (6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, 0<p+q+r+s<2), Li 7-w La3Zr 2-p-q-r-s Nb p Hf q Sc r Mn s O 12 (6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, 0<p+q+r+s<2), or Li 7-w La3Zr 2-p-q-r-s Nb p Hf q Sc r Sn s O 12 (6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, 0<p+q+r+s<2).
[0151] In the solid ionic conductor, for example, the garnet-type oxide represented by Formula 1 may be a garnet-type oxide represented by any one of the following formulas:
[0152] Li 7.5 La3Zr 1.4 Al 0.5 Ir 0.1 O 12 Li 7.5 La3Zr 1.3 Al 0.5 Ir 0.2 O 12 Li 7.5 La3Zr 1.4 Ga 0.5 Ir 0.1 O 12 Li 7.5 La3Zr 1.3 Ga 0.5 Ir 0.2 O 12 Li 6.5 La3Zr 1.4 Ta 0.5 Ir 0.1 O 12 Li 6.5 La3Zr 1.3 Ta 0.5 Ir 0.2 O 12 Li 6.5 La3Zr 1.4 Nb 0.5 Ir 0.1 O 12 Li 6.5 La3Zr 1.3 Nb 0.5 Ir 0.2 O 12 ;
[0153] Li 7.5 La3Zr 1.4 Al 0.5 Ru 0.1 O 12 Li 7.5 La3Zr 1.3 Al 0.5 Ru 0.2 O 12 Li 7.5 La3Zr 1.4 Ga 0.5 Ru 0.1 O 12 Li 7.5 La3Zr 1.3 Ga 0.5 Ru 0.2 O 12 Li 6.5 La3Zr1.4 Ta 0.5 Ru 0.1 O 12 Li 6.5 La3Zr 1.3 Ta 0.5 Ru 0.2 O 12 Li 6.5 La3Zr 1.4 Nb 0.5 Ru 0.1 O 12 Li 6.5 La3Zr 1.3 Nb 0.5 Ru 0.2 O 12 ;
[0154] Li 7.5 La3Zr 1.4 Al 0.5 Mn 0.1 O 12 Li 7.5 La3Zr 1.3 Al 0.5 Mn 0.2 O 12 Li 7.5 La3Zr 1.4 Ga 0.5 Mn 0.1 O 12 Li 7.5 La3Zr 1.3 Ga 0.5 Mn 0.2 O 12 Li 6.5 La3Zr 1.4 Ta 0.5 Mn 0.1 O 12 Li 6.5 La3Zr 1.3 Ta 0.5 Mn 0.2 O 12 Li 6.5 La3Zr 1.4 Nb 0.5 Mn 0.1 O 12 Li 6.5 La3Zr 1.3 Nb 0.5 Mn 0.2 O 12 ;
[0155] Li 7.5 La3Zr 1.4 Al0.5 Sn 0.1 O 12 Li 7.5 La3Zr 1.3 Al 0.5 Sn 0.2 O 12 Li 7.5 La3Zr 1.4 Ga 0.5 Sn 0.1 O 12 Li 7.5 La3Zr 1.3 Ga 0.5 Sn 0.2 O 12 Li 6.5 La3Zr 1.4 Ta 0.5 Sn 0.1 O 12 Li 6.5 La3Zr 1.3 Ta 0.5 Sn 0.2 O 12 Li 6.5 La3Zr 1.4 Nb 0.5 Sn 0.1 O 12 Li 6.5 La3Zr 1.3 Nb 0.5 Sn 0.2 O 12 ;
[0156] Li 7.98 La3Zr 0.49 Al 0.49 Hf 0.49 Sc 0.49 Ir 0.04 O 12 Li 7.95 La3Zr 0.475 Al 0.475 Hf 0.475 Sc 0.475 Ir 0.1 O 12 Li 7.98 La3Zr 0.49 Ga 0.49 Hf 0.49 Sc 0.49 Ir 0.04 O 12 Li 7.95 La3Zr 0.475 Ga 0.475 Hf 0.475Sc 0.475 Ir 0.1 O 12 Li7La3Zr 0.49 Ta 0.49 Hf 0.49 Sc 0.49 Ir 0.04 O 12 Li7La3Zr 0.475 Ta 0.475 Hf 0.475 Sc 0.475 Ir 0.1 O 12 Li7La3Zr 0.49 Nb 0.49 Hf 0.49 Sc 0.49 Ir 0.04 O 12 Li7La3Zr 0.475 Nb 0.475 Hf 0.475 Sc 0.475 Ir 0.1 O 12 ;
[0157] Li 7.98 La3Zr 0.49 Al 0.49 Hf 0.49 Sc 0.49 Ru 0.04 O 12 Li 7.95 La3Zr 0.475 Al 0.475 Hf 0.475 Sc 0.475 Ru 0.1 O 12 Li 7.98 La3Zr 0.49 Ga 0.49 Hf 0.49 Sc 0.49 Ru 0.04 O 12 Li 7.95 La3Zr 0.475 Ga 0.475 Hf 0.475 Sc 0.475 Ru 0.1 O 12 Li7La3Zr 0.49 Ta 0.49 Hf 0.49 Sc 0.49 Ru 0.04 O 12 Li7La3Zr0.475 Ta 0.475 Hf 0.475 Sc 0.475 Ru 0.1 O 12 Li7La3Zr 0.49 Nb 0.49 Hf 0.49 Sc 0.49 Ru 0.04 O 12 Li7La3Zr 0.475 Nb 0.475 Hf 0.475 Sc 0.475 Ru 0.1 O 12 ;
[0158] Li 7.98 La3Zr 0.49 Al 0.49 Hf 0.49 Sc 0.49 Mn 0.04 O 12 Li 7.95 La3Zr 0.475 Al 0.475 Hf 0.475 Sc 0.475 Mn 0.1 O 12 Li 7.98 La3Zr 0.49 Ga 0.49 Hf 0.49 Sc 0.49 Mn 0.04 O 12 Li 7.95 La3Zr 0.475 Ga 0.475 Hf 0.475 Sc 0.475 Mn 0.1 O 12 Li7La3Zr 0.49 Ta 0.49 Hf 0.49 Sc 0.49 Mn 0.04 O 12 Li7La3Zr 0.475 Ta 0.475 Hf 0.475 Sc 0.475 Mn 0.1 O 12 Li7La3Zr 0.49 Nb 0.49 Hf 0.49 Sc 0.49 Mn0.04 O 12 , Li7La3Zr 0.475 Nb 0.475 Hf 0.475 Sc 0.475 Mn 0.1 O 12 ;
[0159] Li 7.98 La3Zr 0.49 Al 0.49 Hf 0.49 Sc 0.49 Sn 0.04 O 12 , Li 7.95 La3Zr 0.475 Al 0.475 Hf 0.475 Sc 0.475 Sn 0.1 O 12 , Li 7.98 La3Zr 0.49 Ga 0.49 Hf 0.49 Sc 0.49 Sn 0.04 O 12 , Li 7.95 La3Zr 0.475 Ga 0.475 Hf 0.475 Sc 0.475 Sn 0.1 O 12 , Li7La3Zr 0.49 Ta 0.49 Hf 0.49 Sc 0.49 Sn 0.04 O 12 , Li7La3Zr 0.475 Ta 0.475 Hf 0.475 Sc 0.475 Sn 0.1 O 12 , Li7La3Zr 0.49 Nb 0.49 Hf 0.49 Sc 0.49 Sn 0.04 O 12 , or Li7La3Zr 0.475 Nb 0.475 Hf 0.475 Sc 0.475 Sn 0.1 O 12 .
[0160] Garnet-type oxides represented by Formula 1 include, for example, a cubic phase and have a garnet or garnet-like crystal structure. While not wishing to be bound by theory, it is understood that, due to the cubic phase, these garnet-type oxides exhibit excellent ionic conductivity and lithium reduction stability.
[0161] Solid ionic conductors comprising garnet-type oxides represented by Formula 1 offer excellent lithium-ion conductivity. Solid ionic conductors comprising garnet-type oxides represented by Formula 1 offer approximately 1 × 10⁻⁶ ppm at room temperature, for example, at approximately 25 °C. - 4 S / cm or higher, approximately 1.5 × 10 -4 S / cm or higher, approximately 2 × 10 -4 S / cm or higher, approximately 2.5 × 10 -4 S / cm or higher, approximately 3 × 10 -4 S / cm or higher, or approximately 3.5 × 10 -4 S / cm or higher. Solid ionic conductors, including garnet-type oxides represented by Formula 1, provide approximately 1 × 10⁻⁶ ions / cm at room temperature, for example, at approximately 25 °C. -4 S / cm to approximately 1×10 -2 S / cm, approximately 1×10 -4 S / cm to approximately 1×10 -3 S / cm, approximately 1.5 × 10 -4 S / cm to approximately 1×10 -3 S / cm, approximately 2×10 -4 S / cm to approximately 1×10 -3 S / cm, approximately 2.5 × 10 -4 S / cm to approximately 1×10 -3 S / cm, approximately 3×10 -4 S / cm to approximately 1×10 -3 S / cm, or approximately 3.5 × 10 -4 S / cm to approximately 1×10 -3 The ionic conductivity is measured in S / cm. The ionic conductivity of the solid ionic conductor can be measured by electrochemical impedance spectroscopy (EIS). See, for example, J.-M. Winand et al., “Measurement of Ionic Conductivity in Electrolytes”, Europhysics Letters, vol. 8, no. 5, pp. 447-452, 1989, the contents of which are incorporated herein by reference.
[0162] Solid ionic conductors comprising garnet-type oxides represented by Formula 1 provide reduced electronic conductivity. Solid ionic conductors comprising garnet-type oxides represented by Formula 1 provide approximately 1 × 10⁻⁶ Ω·cm at room temperature, for example, at approximately 300 K, i.e., approximately 27 °C. -5 mS / cm or less, approximately 0.5 × 10 -5 mS / cm or less, approximately 0.3 × 10 -5 mS / cm or less, approximately 0.2 × 10 -5 mS / cm or less, approximately 0.1 × 10 -5 mS / cm or less, approximately 0.05 × 10 -5 mS / cm or less, or about 0.01×10 -5 Electronic conductivity of mS / cm or less. Therefore, in an electrode assembly comprising a positive electrode, a negative electrode, and a solid ionic conductor comprising a garnet-type oxide represented by Formula 1 and disposed between the positive and negative electrodes, electron transfer between the positive and negative electrodes can be effectively blocked to reduce the possibility of a short circuit between the positive and negative electrodes. The electronic conductivity of the solid ionic conductor can be measured by electrochemical impedance spectroscopy (EIS).
[0163] The activation energy of solid ionic conductors, including garnet-type oxides represented by Formula 1, in the temperature range of about 25°C to about 100°C can be about 0.5 eV or less, about 0.45 eV or less, or about 0.4 eV or less. The activation energy of solid ionic conductors, including garnet-type oxides represented by Formula 1, in the temperature range of about 25°C to about 100°C can be about 0.30 eV to about 0.4 eV, about 0.31 eV to about 0.4 eV, about 0.32 eV to about 0.4 eV, about 0.33 eV to about 0.4 eV, about 0.34 eV to about 0.4 eV, or about 0.35 eV to about 0.4 eV. The activation energy of said solid ionic conductors can be measured by electrochemical impedance spectroscopy (EIS).
[0164] Solid ionic conductors, including garnet-type oxides represented by Formula 1, can appear in Raman spectra at approximately 600 cm⁻¹. -1 Approximately 800cm -1The dominant resonance (i.e., peak) at the point. This peak may be due to bonds between oxygen and metals such as Ir, Ru, Mn, or Sn present on the surface of the solid ionic conductor. Since the solid ionic conductor comprising the garnet-type oxide represented by Formula 1 includes strong peaks on its surface due to Ir-O bonds, Ru-O bonds, Mn-O bonds, Sn-O bonds, etc., the interfacial resistance between the solid ionic conductor represented by Formula 1 and lithium metal can be reduced. For example, it is not desirable to be bound by theory, but it is considered that since the solid ionic conductor comprising the garnet-type oxide represented by Formula 1 has Ir-O bonds, Ru-O bonds, Mn-O bonds, Sn-O bonds, etc. in high content on its surface, the solid ionic conductor can act as a catalyst for electrode reactions. Alternatively, it is not desirable to be bound by theory, but it is considered that the affinity between the solid ionic conductor comprising the garnet-type oxide represented by Formula 1 and lithium can be increased, and as a result, the interfacial resistance to lithium metal can be reduced. Therefore, the internal resistance of a secondary battery including a solid ionic conductor as described in this disclosure can be reduced, and the charge-discharge characteristics of the secondary battery can be improved.
[0165] At a temperature of 25°C and at approximately 0.1 Hz to approximately 10 6 When measured by impedance spectroscopy in a lithium-symmetric cell with lithium metal electrodes disposed between them within a frequency range of Hz, the interfacial resistance between the solid ionic conductor and the lithium metal can be, for example, approximately 1 ohm square centimeter (Ω·cm). 2 (approximately 80 Ω·cm) 2 Approximately 1 Ω·cm 2 Approximately 75 Ω·cm 2 Approximately 1 Ω·cm 2 Approximately 70 Ω·cm 2 Approximately 1 Ω·cm 2 Approximately 65 Ω·cm 2 Approximately 1 Ω·cm 2 Approximately 60Ω·cm 2 Approximately 1 Ω·cm 2 Approximately 55Ω·cm 2 Approximately 1 Ω·cm 2 Approximately 50 Ω·cm 2 Approximately 1 Ω·cm 2 Approximately 45Ω·cm 2 or approximately 1 Ω·cm 2 Approximately 40Ω·cm 2 Because the solid ionic conductor has such low interfacial resistance, the charge-discharge characteristics of the secondary battery including the solid ionic conductor are further improved.
[0166] The garnet-type oxide represented by Formula 1 may be in the form of particles. The average particle diameter of the particles is, for example, about 5 nanometers (nm) to about 500 micrometers (μm), about 100 nm to about 100 μm, or about 1 μm to about 50 μm, and the specific surface area thereof is, for example, about 0.01 square meters per gram (m 2 / g) to about 1000 m 2 / g, or about 0.5 m 2 / g to about 100 m 2 / g. The average particle diameter of the garnet-type oxide represented by Formula 1 is, for example, the median diameter (D50) measured using a laser particle size distribution analyzer.
[0167] Solid Electrolyte
[0168] A solid electrolyte according to another embodiment includes a solid ionic conductor comprising the garnet-type oxide represented by Formula 1. By including such a solid ionic conductor, the solid electrolyte may have high ionic conductivity and low interfacial resistance. Accordingly, the solid electrolyte including the solid ionic conductor comprising the garnet-type oxide represented by Formula 1 can be used as an electrolyte for an electrochemical device.
[0169] In addition to the solid ionic conductor comprising the garnet-type oxide represented by Formula 1, the solid electrolyte may include a second solid electrolyte. For example, the solid electrolyte may additionally include a sulfide-based solid electrolyte and / or an oxide-based solid electrolyte. Examples may include, but are not limited to, Li3N, lithium super ionic conductor (LISICON), LIPON (Li 3-y PO 4-x N x , 0<y<3, 0<x<4), thio-LISICON (Li 3.25 Ge 0.25 P 0.75 S4), Li2S, Li2S-P2S5, Li2S-SiS2, Li2S-GeS2, Li2S-B2S3, Li2S-Al2S3, Li2O-Al2O3-TiO2-P2O5 (LATP), or a crystalline thioantimonic silver ore-type solid ionic conductor. Any suitable solid ionic conductor may be used.
[0170] The crystalline thioantimonic silver ore-type solid ionic conductor is, for example, a solid ionic conductor having a composition represented by Formula 8 and a suitable crystallinity. The crystalline thioantimonic silver ore-type solid ionic conductor may be obtained by heat treatment at a high temperature of 550°C or higher.
[0171] Formula 8
[0172] Li 12-n-x AX 6-x Y’ x
[0173] In Equation 8,
[0174] A is P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb or Ta,
[0175] X is S, Se, Te, or a combination thereof.
[0176] Y' is Cl, Br, I, F, CN, OCN, SCN, N3, or a combination thereof, and
[0177] The following conditions must be met: 0 ≤ x ≤ 2. n is the oxidation number of A, the oxidation number of X is -2, and the oxidation number of Y' is -1.
[0178] The sulfide-germanium type solid ionic conductor includes Li 7-x PS 6-x Cl x (0≤x≤2), Li 7-x PS 6-x Br x (0≤x≤2), Li 7-x PS 6-x I x (0≤x≤2), or combinations thereof. In particular, the argentite-germanium ore-type solid ionic conductor comprises Li6PS5Cl, Li6PS5Br, Li6PS5I, or combinations thereof. The elastic modulus of the crystalline argentite-germanium ore-type solid ionic conductor is, for example, 30 gigapascals (GPa) or higher.
[0179] The solid electrolyte may be in the form of a powder, or it may be in the form of a molded or monolithic form. The molded form of the solid electrolyte may be, for example, a disc, a sheet, a film, etc., but its form is not limited to these, and it may have any suitable form depending on the intended use.
[0180] In addition to the solid ionic conductor represented by Formula 1, the solid electrolyte may further include an impurity phase. This impurity phase may be generated during the process of preparing the solid ionic conductor.
[0181] Electrochemical device
[0182] The electrochemical device according to the embodiments includes a solid ionic conductor comprising a garnet-type oxide represented by Formula 1, and includes a positive electrode, a negative electrode, and a solid electrolyte.
[0183] Since the electrochemical device comprises a solid ionic conductor including a garnet-type oxide represented by Formula 1, the lithium-ion conductivity of the electrochemical device is improved and its interfacial resistance to lithium metal is reduced.
[0184] At least one of the cathode, cathode, solid electrolyte, or combinations thereof included in the electrochemical device may comprise a solid ionic conductor comprising a garnet-type oxide represented by Formula 1. The electrochemical device may further comprise a cathode protective layer, a cathode protective layer, a solid electrolyte protective layer, or combinations thereof. The cathode protective layer, cathode protective layer, solid electrolyte protective layer, or combinations thereof may comprise a solid ionic conductor comprising a garnet-type oxide represented by Formula 1.
[0185] For example, the solid electrolyte of the electrochemical device may comprise a solid ionic conductor including a garnet-type oxide represented by Formula 1. The solid ionic conductor may be included in a solid electrolyte layer, a solid electrolyte protective layer, a positive electrode protective layer, a negative electrode protective layer, or a combination thereof. The solid electrolyte protective layer may be a layer that is on the solid electrolyte layer and includes the solid ionic conductor, for example, to provide a protected solid electrolyte layer. The positive electrode protective layer may be a layer that is on the positive electrode and includes the solid ionic conductor, for example, to provide a protected positive electrode. The negative electrode protective layer may be a layer that is on the negative electrode and includes the solid ionic conductor, for example, to provide a protected negative electrode.
[0186] For example, the solid electrolyte layer disposed between the positive and negative electrodes of the electrochemical device may contain a solid ionic conductor comprising a garnet-type oxide represented by Formula 1.
[0187] For example, a solid ionic conductor comprising a garnet-type oxide represented by Formula 1 may be disposed on one surface of at least one of the positive electrode, negative electrode, or solid electrolyte of the electrochemical device.
[0188] The electrochemical device provides improved charge-discharge characteristics because the solid electrolyte layer (i.e., protective layer) comprising a garnet-type oxide represented by Formula 1 provides improved lithium-ion conductivity and low interfacial resistance to lithium metal.
[0189] For example, a solid electrolyte layer comprising a garnet-type oxide represented by Formula 1 is disposed on one surface of the negative electrode to form a negative electrode protective layer, and the negative electrode may comprise lithium metal, lithium metal alloy, or a combination thereof.
[0190] The electrochemical device may be, for example, an all-solid-state secondary battery or a metal-air battery, but is not limited thereto. Any electrochemical device may be used, provided it is applicable in the art.
[0191] The following text will describe all-solid-state secondary batteries in more detail.
[0192] Reference Figure 5-7, the all-solid secondary battery 1 includes a positive electrode 10 including a positive active material layer 12, a negative electrode 20, and a solid electrolyte layer 30 between the positive electrode 10 and the negative electrode 20. The negative electrode 20 includes a negative current collector 21 and a first negative active material layer 22 disposed on the negative current collector 21. The first negative active material layer 22 includes a negative active material that forms an alloy or compound with lithium. At least one of the positive electrode 10, the negative electrode 20, and the solid electrolyte layer of the all-solid secondary battery 1 includes a solid ion conductor including a garnet-type oxide represented by Formula 1.
[0193] Solid electrolyte layer
[0194] Reference Figure 5-7 , the solid electrolyte layer 30 is disposed between the positive electrode 10 and the negative electrode 20, and includes a solid electrolyte.
[0195] The solid electrolyte included in the solid electrolyte layer 30 includes a solid ion conductor including a garnet-type oxide represented by Formula 1.
[0196] The solid electrolyte layer 30 may further include a second solid electrolyte together with the solid ion conductor including the garnet-type oxide represented by Formula 1. The second solid electrolyte is, for example, a sulfide-based solid electrolyte, an oxide-based solid electrolyte, or a combination thereof. The second solid electrolyte is, for example, an oxide-based solid electrolyte.
[0197] The oxide-based solid electrolyte may be Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (0<x<2, 0≤y<3), BaTiO3, Pb(Zr in which 0≤a≤1 1-a Ti a )O3(PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT)(0≤x<1, 0≤y<1), Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3(PMN-PT), HfO2, SrTiO3, SnO2, CeO2, Na2O, MgO, NiO, CaO, BaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiO2, Li3PO4, Li x Ti y (PO4)3(0<x<2, 0<y<3), Li x Al y Tiz (PO4)3(0<x<2, 0<y<1, 0<z<3), Li 1+x+y (Al a Ga 1-a ) x (Ti b Ge 1-b ) 2-x Si y P 3-y O 12 (0≤x≤1, 0≤y≤1, 0≤a≤1, 0≤b≤1), Li x La y TiO3(0<x<2, 0<y<3), Li2O, LiOH, Li2CO3, LiAlO2, Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2, or Li 3+x La3M2O 12 (M=Te, Nb, or Zr, 0≤x≤10). The solid electrolyte may be prepared by a sintering method. The oxide-based solid electrolyte is for example a garnet-type solid electrolyte, for example, Li7La3Zr2O 12 (LLZO) or Li 3+x La3Zr 2- a M a O 12 (M-doped LLZO, M=Ga, W, Nb, Ta, or Al, 0≤x≤10).
[0198] The second solid electrolyte is for example a sulfide-based solid electrolyte. The sulfide-based solid electrolyte is for example at least one of the following: Li2S-P2S5, Li2S-P2S5-LiX (X is a halogen element), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (m and n are each positive numbers, and Z is Ge, Zn, or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (p and q are each positive numbers, and M is P, Si, Ge, B, Al, Ga, or In), Li 7-x PS 6-x Clx (0≤x≤2), Li 7-x PS 6-x Br x (0≤x≤2), or Li 7-x PS 6-x I x (0≤x≤2). The sulfide-based solid electrolyte is prepared by treating the starting material, such as Li₂S or P₂S₅, by melt quenching or mechanical grinding. Following this treatment, heat treatment may be performed. The sulfide-based solid electrolyte may be amorphous, crystalline, or a mixture thereof. Further, the sulfide-based solid electrolyte may include at least sulfur (S), phosphorus (P), and lithium (Li) as components of the aforementioned materials of the sulfide-based solid electrolyte. For example, the sulfide-based solid electrolyte may include Li₂S-P₂S₅. When Li₂S-P₂S₅ is used as the material of the sulfide-based solid electrolyte, the molar ratio of Li₂S to P₂S₅ is, for example, in the range of Li₂S:P₂S₅ = 50:50 to 90:10.
[0199] The sulfide-based solid electrolyte may include, for example, a sulfide-germanium ore type solid electrolyte represented by Formula 9:
[0200] Formula 9
[0201] Li 12-n-x AX 6-x Y' x
[0202] In Equation 9, A is P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb, or Ta; X is S, Se, Te, or a combination thereof; and Y' is Cl, Br, I, F, CN, OCN, SCN, N3, or a combination thereof, satisfying 1≤n≤5 and 0≤x≤2. The oxidation number of A is +n, the oxidation number of X is -2, and the oxidation number of Y' is -1.
[0203] The sulfide-based solid electrolyte may include Li 7-x PS 6-x Cl x (0≤x≤2), Li 7-x PS 6-x Br x (0≤x≤2), or Li 7-x PS 6-x I x At least one sulfide-germanium ore type compound of (0≤x≤2). In particular, the sulfide-based solid electrolyte may be at least one sulfide-germanium ore type compound including Li6PS5Cl, Li6PS5Br, or Li6PS5I.
[0204] The solid electrolyte layer 30 may further include an adhesive. Examples of adhesives included in the solid electrolyte layer 30 may include, but are not limited to, styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, and polyethylene. Any adhesive may be used, provided it is applicable in the art. The adhesive of the solid electrolyte layer 30 may be the same as or different from the adhesive of the positive electrode active material layer 12 and the adhesive of the negative electrode active material layer 22.
[0205] The solid electrolyte layer 30 is formed by depositing a solid electrolyte comprising the solid ionic conductor using a film-forming method such as aerosol deposition, cold spraying, or sputtering. Alternatively, the solid electrolyte layer 30 can be formed by pressing individual solid electrolyte particles. Alternatively, the solid electrolyte layer 30 can be formed by applying a mixture of solid electrolyte, solvent, and binder, and then drying and pressing the applied mixture.
[0206] Positive electrode layer
[0207] The positive electrode 10 includes a positive electrode current collector 11 and a positive electrode active material layer 12.
[0208] The positive current collector 11 may be, for example, a plate or foil comprising: indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or alloys thereof. The positive current collector 11 may be omitted.
[0209] The positive electrode active material layer 12 includes, for example, a positive electrode active material.
[0210] The positive electrode active material is a positive electrode active material capable of reversibly absorbing and desorbing lithium ions. Examples of the positive electrode active material may include, but are not limited to: lithium transition metal oxides such as lithium cobalt oxide (LCO), lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminum oxide (NCA), lithium nickel cobalt manganese oxide (NCM), lithium manganese oxide, and lithium iron phosphate; nickel sulfide; copper sulfide; lithium sulfide; iron oxide; and vanadium oxide. Any positive electrode active material may be used, provided it is applicable in the art. These positive electrode active materials may be used alone or as a mixture of two or more positive electrode active materials.
[0211] The positive electrode active material may include a lithium salt of a transition metal oxide having a layered rock-salt structure. The lithium transition metal oxide having a layered rock-salt structure is, for example, a ternary lithium transition metal oxide such as LiNi. x Co y Al z O2(NCA) or LiNi x Co yMn z O₂(NCM) (0<x<1, 0<y<1, 0<z<1, x+y+z=1). When the positive electrode active material includes the ternary lithium transition metal oxide having a layered rock-salt structure, the energy density and thermal stability of the all-solid secondary battery 1 can be further improved.
[0212] As described, the positive electrode active material may be covered with a coating layer. Any coating layer may be used without limitation, as long as it is known as a coating layer for a positive electrode active material of an all-solid secondary battery. The coating layer may include, for example, Li₂O-ZrO₂.
[0213] When the positive electrode active material includes nickel (Ni) as a ternary lithium transition metal oxide such as NCA or NCM, the capacity density of the all-solid secondary battery 1 may be increased, and further, when the positive electrode active material is covered with a coating layer such as Li₂O-ZrO₂, elution of metals in the positive electrode active material in a charged state may be reduced. As a result, the cycle characteristics of the all-solid secondary battery 1 may be improved.
[0214] The shape of the positive electrode active material is, for example, a particulate shape such as a spherical sphere or an elliptical sphere. The particle diameter of the positive electrode active material is not particularly limited, and is within the range applicable to positive electrode active materials of conventional all-solid secondary batteries. The content of the positive electrode active material in the positive electrode 10 is also not particularly limited, and is within the range applicable to positive electrode layers of conventional all-solid secondary batteries.
[0215] In addition to the positive electrode active material, the positive electrode 10 may further include additives such as a conductive agent, a binder, a filler, a dispersant, and an ion conduction auxiliary agent. Examples of the conductive agent include graphite, carbon black, acetylene black, Ketjen black, carbon fiber, and metal powder. Examples of the binder include styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, and polyethylene. As the filler, coating agent, dispersant, ion conduction auxiliary agent, and the like that can be blended into the positive electrode 10, known materials commonly used for electrodes of solid secondary batteries may be used.
[0216] The positive electrode 10 may further include a solid ion conductor containing a garnet-type oxide represented by Formula 1 as a solid electrolyte. The solid electrolyte included in the positive electrode 10 may be the same (similar to) as or different from the solid electrolyte 30 included in the solid electrolyte layer.
[0217] The positive electrode 10 may be prepared by, for example, the following method.
[0218] A slurry is prepared by mixing a positive electrode active material, a carbon-based conductive material, and a binder, which constitute the positive electrode active material layer 12. The prepared slurry is applied to a positive electrode current collector 11 and then dried to obtain a laminate. The obtained laminate is pressed to prepare a positive electrode 10. The pressing is a pressing using isostatic pressure, such as rolling or flat pressing, but is not limited thereto. Any pressing method can be used, as long as it is applicable in the art. The pressing process can be omitted. Alternatively, the positive electrode 10 is prepared by compacting the mixture of materials constituting the positive electrode active material layer 12 into a disc or stretching (forming) the mixture into a sheet. When the positive electrode 10 is prepared by this method, the positive electrode current collector 11 can be omitted.
[0219] negative electrode layer
[0220] The negative electrode 20 includes a negative electrode current collector 21 and a first negative electrode active material layer 22.
[0221] The negative electrode current collector 21 is made of, for example, a material that does not react with lithium, i.e., a material that does not form alloys or compounds. Examples of materials constituting the negative electrode current collector 21 include, but are not limited to, copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), and nickel (Ni). Any material can be used, provided it is used as an electrode current collector in the art. The negative electrode current collector 21 may be formed from one of the aforementioned metals, or may be formed from an alloy or coating material of two or more of the aforementioned metals. The negative electrode current collector 21 has, for example, a plate shape or a foil shape. The negative electrode current collector 21 may be omitted.
[0222] The first negative electrode active material layer 22 may include at least one negative electrode active material selected from carbon-based negative electrode active materials and metal or quasi-metal negative electrode active materials.
[0223] The metallic or quasi-metallic anode active material may have a higher lithium-ion diffusion coefficient than that of lithium metal. This results in lithium diffusing into the first anode active material layer 22 rapidly passing through it and depositing as a uniform lithium metal layer between the first anode active material layer 22 and the anode current collector 21.
[0224] The metallic or quasi-metallic anode active material may include, but is not limited to, at least one selected from: indium (In), silicon (Si), gallium (Ga), tin (Sn), aluminum (Al), titanium (Ti), zirconium (Zr), niobium (Nb), germanium (Ge), antimony (Sb), bismuth (Bi), gold (Au), platinum (Pt), palladium (Pd), magnesium (Mg), palladium (Pd), silver (Ag), and zinc (Zn), and any metallic or quasi-metallic anode active material may be used, provided that it forms an alloy or compound with lithium in the art. For example, nickel (Ni) is not a metallic anode active material because it does not form an alloy with lithium.
[0225] The carbon-based negative electrode active material is crystalline carbon or amorphous carbon. The crystalline carbon is, for example, graphite.
[0226] Specifically, the carbon-based positive electrode active material is amorphous carbon. Examples of amorphous carbon include, but are not limited to, carbon black (CB), acetylene black (AB), furnace black (FB), Ketjen black (KB), graphene, carbon nanotubes, or carbon nanofibers. Any amorphous carbon can be used, provided it is classified as amorphous carbon in the art. Amorphous carbon has no crystallinity or very low crystallinity and is different from crystalline carbon or graphite-based carbon.
[0227] The negative electrode active material included in the first negative electrode active material layer 22 has, for example, a particulate shape. The average particle size of the negative electrode active material having a particulate shape is, for example, about 4 μm or less, about 3 μm or less, about 2 μm or less, about 1 μm or less, or about 900 nm or less. The average particle size of the negative electrode active material having a particulate shape is, for example, about 10 nm to about 4 μm, about 10 nm to about 3 μm, about 10 nm to about 2 μm, about 10 nm to about 1 μm, or about 10 nm to about 900 nm. Because the negative electrode active material has an average particle size within this range, lithium can be more easily and reversibly absorbed and / or desorbed during charging and discharging. The average particle size of the negative electrode active material is, for example, the median diameter (D50) measured using a laser particle size analyzer.
[0228] The first negative electrode active material layer 22 comprises one such negative electrode active material, or a mixture of different such negative electrode active materials. The mixing ratio of the amorphous carbon to the metal or metalloid mixture is, for example, 10:1 to 1:2, 5:1 to 1:1, or 4:1 to 2:1 by weight, but is not limited to this range, and is selected according to the desired characteristics of the all-solid-state secondary battery 1. Because the negative electrode active material has such a composition, the cycle characteristics of the all-solid-state secondary battery 1 can be further improved.
[0229] The first negative electrode active material layer 22 may further include, for example, an adhesive. Examples of such adhesives include, but are not limited to, styrene-butadiene rubber (SBR), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyethylene, vinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile, and polymethyl methacrylate. Any adhesive may be used, provided it is applicable in the art. The adhesive may be used alone or in combination of different adhesives. The adhesive may be, for example, an aqueous adhesive or a non-aqueous adhesive. The aqueous adhesive is used in a state dissolved in water or in a state dispersed in water. The non-aqueous adhesive is used in a state dissolved in an organic solvent.
[0230] The thickness of the first negative electrode active material layer 22 is, for example, about 50% or less, about 40% or less, about 30% or less, about 20% or less, about 10% or less, or about 5% or less of the thickness of the positive electrode active material layer. The thickness of the first negative electrode active material layer 22 is, for example, about 1 μm to about 50 μm, about 1 μm to about 40 μm, about 1 μm to about 20 μm, about 2 μm to about 15 μm, about 3 μm to about 10 μm, or about 5 μm to about 10 μm. When the thickness of the first negative electrode active material layer 22 is too thin, lithium dendrites formed between the first negative electrode active material layer 22 and the negative electrode current collector 21 cause the first negative electrode active material layer 22 to collapse, making it difficult to improve the cycle characteristics of the solid secondary battery 1. When the thickness of the first negative electrode active material layer 22 is excessively increased, the energy density of the all-solid-state secondary battery 1 decreases, and the internal resistance of the all-solid-state secondary battery 1 increases due to the first negative electrode active material layer 22, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1.
[0231] The first negative electrode active material layer 22 may further include additives such as fillers, dispersants and ion conductors used in conventional all-solid-state secondary batteries.
[0232] Reference Figure 6 The all-solid-state secondary battery 1 further includes, for example, a thin film 23 containing elements capable of forming an alloy with lithium, on a negative electrode current collector 21. The thin film 23 is disposed between the negative electrode current collector 21 and a first negative electrode active material layer 22. The thin film 23 contains, for example, elements capable of forming an alloy with lithium. Examples of elements capable of forming an alloy with lithium include, but are not limited to, gold, silver, zinc, tin, indium, silicon, aluminum, and bismuth. Any element can be used, as long as it can form an alloy with lithium. The thin film 23 is formed from one of these metals, or from an alloy of several metals. Because the thin film 23 is disposed on the negative electrode current collector 21, for example, the deposition form of a second negative electrode active material layer (not shown) deposited between the thin film 23 and the first negative electrode active material layer 22 can be further flattened, and the cycle characteristics of the all-solid-state secondary battery 1 can be further improved.
[0233] The thickness of the thin film 23 is, for example, about 1 nm to about 800 nm, about 10 nm to about 700 nm, about 50 nm to about 600 nm, or about 100 nm to about 500 nm. When the thickness of the thin film 23 is less than 1 nm, it is difficult for the thin film 23 to exert its function. When the thickness of the thin film 23 is too thick, the thin film 23 itself absorbs lithium to reduce the amount of lithium deposited (i.e., deposited) at the negative electrode, thereby reducing the energy density of the all-solid-state battery and degrading the cycle characteristics of the all-solid-state secondary battery 1. The thin film 23 can be deposited on the negative electrode current collector 21 by, for example, vacuum deposition, sputtering, or plating, but the deposition method is not limited to this method, and any method in the art capable of forming the thin film 23 can be used. The thin film 23 can be, for example, a plating layer.
[0234] Reference Figure 7 The all-solid-state secondary battery 1 further includes, for example, a second negative electrode active material layer 24 disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22. The second negative electrode active material layer 24 may be plated between the negative electrode current collector 21 and the first negative electrode active material layer 22. The second negative electrode active material layer 24 is a metal layer comprising lithium or a lithium alloy. The second negative electrode active material layer 24 may be a plating layer. The metal layer comprises lithium or a lithium alloy. Therefore, since the second negative electrode active material layer 24 is a lithium-containing metal layer, it acts as, for example, a lithium reservoir. Examples of the lithium alloy include, but are not limited to: Li-Al alloys, Li-Sn alloys, Li-In alloys, Li-Ag alloys, Li-Au alloys, Li-Zn alloys, Li-Ge alloys, and Li-Si alloys. Any lithium alloy may be used, provided it is used in the art. The second negative electrode active material layer 24 may be formed from one of these alloys or lithium, or may be formed from several alloys. Although not shown in the figure, the all-solid-state secondary battery 1 may further include, for example, a second negative electrode active material layer 24 disposed between the first negative electrode active material layer 22 and the solid electrolyte layer 30. The second negative electrode active material layer 24 may be deposited between the first negative electrode active material layer 22 and the solid electrolyte layer 30.
[0235] The thickness of the second negative electrode active material layer 24 is not particularly limited, but can be, for example, about 1 μm to about 1000 μm, about 1 μm to about 500 μm, about 1 μm to about 200 μm, about 1 μm to about 150 μm, about 1 μm to about 100 μm, or about 1 μm to about 50 μm. When the thickness of the second negative electrode active material layer 24 is too thin, it is difficult for it to function as a lithium reservoir. When the thickness of the second negative electrode active material layer 24 is too thick, there is a possibility that the mass and volume of the all-solid-state secondary battery 1 increases and its cycle characteristics may deteriorate. The second negative electrode active material layer 24 can be, for example, a metal foil having a thickness within the above range. When fabricating the negative electrode 20, the second negative electrode active material layer 24 can be disposed on the negative electrode current collector 21.
[0236] The negative electrode 20 can be prepared by the following method.
[0237] A slurry is prepared by adding a negative electrode active material, a conductive material, and a binder, which constitute the first negative electrode active material layer 22, to a polar or non-polar solvent. The prepared slurry is applied to a peelable substrate, such as a negative electrode current collector 21, and dried to deposit the first negative electrode active material layer 22 onto the negative electrode current collector 21. The first negative electrode active material layer 22 is then pressed to prepare a negative electrode 20, which is a laminate of the negative electrode current collector 21 and the first negative electrode active material layer 22. The pressing is performed using isostatic pressure, such as rolling or flat pressing, but is not limited thereto. Any pressing method can be used, as long as it is applicable in the art. The pressing can be performed at a temperature of room temperature to about 90°C or lower, for example, from about 20°C to about 90°C. Alternatively, pressing can be performed at a high temperature of about 100°C or higher. The pressing process can be omitted.
[0238] Manufacturing of all-solid-state secondary batteries
[0239] The positive electrode 10, negative electrode 20, and solid electrolyte layer prepared by the above method are stacked, with solid electrolyte 30 between the positive electrode 10 and negative electrode 20, and then pressed to manufacture an all-solid-state secondary battery 1. The pressing process can be omitted.
[0240] Methods for preparing solid ionic conductors
[0241] A method for preparing a solid ionic conductor according to an embodiment includes: providing a precursor mixture comprising a precursor for forming a solid ionic conductor; and heat-treating the precursor mixture under an oxidizing atmosphere to provide a solid ionic conductor comprising a garnet-type oxide represented by Formula 1.
[0242] When preparing the precursor mixture, Li precursor, La precursor, Zr precursor, M1 precursor, M2 precursor, M3 precursor, M4 precursor and X precursor can be mixed.
[0243] In Equation 1, when B = 0, the precursor M1 is omitted; when D = 0, the precursor M2 is omitted; and when I = 0, the precursor X can be omitted.
[0244] The lithium precursors include oxides, nitrides, oxynitrides, nitrates, hydroxides, or carbonates, each containing lithium. Examples include lithium carbonate and lithium nitrate.
[0245] Precursor compounds containing monovalent cations include oxides, nitrides, oxynitrides, nitrates, hydroxides, or carbonates containing elements such as Na, K, Rb, Cs, H, or Fr.
[0246] Precursor compounds containing divalent cations include oxides, nitrides, oxynitrides, nitrates, hydroxides, or carbonates containing elements such as Mg, Ca, Ba, or Sr.
[0247] Precursor compounds containing trivalent cations include oxides, nitrides, oxynitrides, nitrates, hydroxides, or carbonates containing elements such as In, Sc, Cr, Au, B, Al, or Ga.
[0248] Precursor compounds containing tetravalent cations include oxides, nitrides, oxynitrides, nitrates, hydroxides, or carbonates containing elements such as Sn, Ti, Mn, Ir, Ru, Pd, Mo, Hf, Ge, V, or Si.
[0249] Precursor compounds containing pentavalent cations include oxides, nitrides, oxynitrides, nitrates, hydroxides, or carbonates containing elements such as Nb, Ta, Sb, V, or P.
[0250] Garnet-type oxides represented by Formula 1 can be prepared by combining precursor compounds in appropriate amounts, such as stoichiometric amounts, to form a mixture, and then subjecting the mixture to heat treatment. The combination may include grinding, such as ball milling, or pulverizing.
[0251] A mixture of precursors with stoichiometric composition can undergo preliminary heat treatment in an oxidizing atmosphere to prepare a preliminary heat-treated product. The preliminary heat treatment can be carried out at a temperature range of about 600°C to about 1100°C for about 1 hour to about 36 hours.
[0252] The preliminary heat treatment may be performed, for example, at about 600°C to about 1100°C, about 700°C to about 1100°C, about 800°C to about 1050°C, about 900°C to about 1050°C, or about 950°C to about 1050°C. The preliminary heat treatment time is about 1 hour to about 36 hours, about 2 hours to about 24 hours, about 4 hours to about 20 hours, about 8 hours to about 16 hours, or about 10 hours to about 14 hours. During the preliminary heat treatment of the mixture, the heating rate of the mixture may be about 1°C / min to about 10°C / min.
[0253] The method for preparing a solid ionic conductor may further include: molding the solid ionic conductor to prepare a molded product after subjecting the precursor mixture to the preliminary heat treatment in an oxidizing atmosphere; and subjecting the molded product to a secondary heat treatment at about 900°C to about 1500°C to prepare a sintered product, wherein the secondary heat treatment of the molded product is performed at a temperature higher than the preliminary heat treatment temperature of the precursor mixture. For example, the secondary heat treatment temperature is higher than the preliminary heat treatment temperature.
[0254] The preliminary heat-treated product can be pulverized. Pulverization can be performed by dry pulverization or wet pulverization. Wet pulverization can be performed, for example, by mixing a solvent, such as methanol, with the preliminary heat-treated product, and then grinding the mixture using a ball mill or similar mill for about 0.5 hours to about 10 hours. Dry pulverization can be performed by grinding using a ball mill or similar mill without a solvent. The particle size of the pulverized preliminary heat-treated product can be about 0.1 μm to about 10 μm, or about 0.1 μm to about 5 μm. The pulverized preliminary heat-treated product can be dried.
[0255] The pulverized preliminary heat-treated product can be mixed with a binder solution and formed into a disc, or it can be rolled into a disc for about 1 minute to about 10 minutes without a binder under a pressure of about 1 ton to about 10 tons.
[0256] The molded product may be subjected to a secondary heat treatment at a temperature of about 900°C to about 1500°C for about 1 hour to about 36 hours. A sintered product is obtained through the secondary heat treatment.
[0257] The secondary heat treatment may be performed at approximately 900°C to approximately 1400°C, approximately 950°C to approximately 1350°C, approximately 1000°C to approximately 1300°C, or approximately 1100°C to approximately 1300°C. The duration of the secondary heat treatment is approximately 1 hour to approximately 36 hours, approximately 1 hour to approximately 24 hours, approximately 1 hour to approximately 12 hours, approximately 1 hour to approximately 10 hours, or approximately 2 hours to approximately 6 hours.
[0258] To obtain the sintered product, the secondary heat treatment temperature is higher than the primary heat treatment temperature. For example, the secondary heat treatment temperature may be about 10°C or more, about 20°C or more, about 30°C or more, or about 50°C or more higher than the primary heat treatment temperature.
[0259] The disc can be subjected to secondary heat treatment in at least one of an oxidizing atmosphere or a reducing atmosphere.
[0260] The secondary heat treatment can be carried out in an a) oxidizing atmosphere, b) a reducing atmosphere, or c) a combination of oxidizing and reducing atmospheres. The secondary heat treatment atmosphere can be selected based on the composition of the precursor included in the solid ionic conductor.
[0261] a) An oxidizing atmosphere is an atmosphere containing an oxidizing gas. The oxidizing gas is, for example, oxygen or air, but is not limited to oxygen or air, and any oxidizing gas can be used, provided it is applicable in the art. The oxidizing atmosphere may be a mixture of an oxidizing gas and an inert gas. The same inert gas used in a reducing atmosphere can be used as the inert gas.
[0262] (b) A reducing atmosphere is an atmosphere containing a reducing gas. The reducing gas is, for example, hydrogen (H2), but is not limited to hydrogen, and any reducing gas may be used, provided it is applicable in the art. The reducing atmosphere may be a mixture of a reducing gas and an inert gas. The inert gas is, for example, nitrogen and argon, but is not limited to these, and any inert gas may be used, provided it is applicable in the art. The content of the reducing gas in the reducing atmosphere is, for example, from about 1% to about 99% of the total gas content, from about 2% to about 50%, or from about 5% to about 20%.
[0263] c) The step of performing secondary heat treatment in an oxidizing atmosphere and a reducing atmosphere refers to the step of performing secondary heat treatment in the following manner: wherein heat treatment in an oxidizing atmosphere and heat treatment in a reducing atmosphere are performed sequentially. The oxidizing atmosphere and the reducing atmosphere are the same as those described in a) and b) above.
[0264] The present disclosure will be described in more detail below with reference to embodiments and comparative examples. However, these embodiments and comparative examples are intended to illustrate technical concepts, and the scope of the present disclosure is not limited thereto.
[0265] Example
[0266] Preparation of solid ionic conductors
[0267] Example 1: Li 6.5 La3Zr 1.4 Ta 0.5 Ru 0.1 O 12 Preparation
[0268] Preparation of solid ionic conductor powder
[0269] Lithium precursor Li₂O, lanthanum precursor La₂O₃, zirconium precursor ZrO₂, tantalum precursor Ta₂O₅, and ruthenium precursor RuO₂ were combined in stoichiometric ratio and then mixed using a planetary mill (Pulverisette 7 premium line) for 10 minutes and allowed to stand for 5 minutes. This cycle was repeated 12 times to obtain a precursor mixture. The obtained precursor mixture was then pre-heat-treated at 1000°C for 12 hours at a heating rate of 5°C / min to prepare a solid ionic conductor powder. The prepared solid ionic conductor powder has a composition of Li₂O₃. 6.5 La3Zr 1.4 Ta 0.5 Ru 0.1 O 12 .
[0270] Preparation of solid ionic conductor wafers
[0271] The prepared solid ionic conductor powder was placed in a die-making machine with a diameter of 1 inch, and a weight of 5 tons was applied using uniaxial pressure for 2 minutes to obtain a disc-shaped wafer. The obtained wafer was placed on an MgO single crystal and covered with the pre-heat-treated solid ionic conductor powder to prevent lithium volatilization and compositional changes. Subsequently, the resulting product was subjected to a second heat treatment at 1200°C for 4 hours at a heating rate of 5°C / min to prepare the solid ionic conductor wafer.
[0272] Example 2: Li 6.5 La3Zr 1.3 Ta 0.5 Ru 0.2 O 12 Preparation
[0273] Solid ionic conductors were prepared in the same manner as in Example 1, except that the stoichiometric ratio of ZrO2 and RuO2 was changed.
[0274] The prepared solid ionic conductor has the composition of Li 6.5 La3Zr 1.3 Ta 0.5 Ru 0.2 O 12 .
[0275] Example 3: Li 6.5 La3Zr 1.4 Ta 0.5 Ir 0.1 O 12 Preparation
[0276] The solid ionic conductor was prepared in the same manner as in Example 1, except that a mixture of Li₂O, La₂O₃, ZrO₂, Ta₂O₅, and IrO₂ was used instead of a mixture of Li₂O, La₂O₃, ZrO₂, Ta₂O₅, and RuO₂ as the precursor mixture. The prepared solid ionic conductor had a composition of Li 6.5 La3Zr 1.4 Ta 0.5 Ir 0.1 O 12 .
[0277] Example 4: Li 6.5 La3Zr 1.3 Ta 0.5 Ir 0.2 O 12 Preparation
[0278] Solid ionic conductors were prepared in the same manner as in Example 3, except that the stoichiometric ratio of ZrO2 and IrO2 was changed.
[0279] The prepared solid ionic conductor has the composition of Li 6.5 La3Zr 1.3 Ta 0.5 Ir 0.2 O 12 .
[0280] Example 5: Li 6.5 La3Zr 1.4 Ta 0.5 Mn 0.1 O 12 Preparation
[0281] The solid ionic conductor was prepared in the same manner as in Example 1, except that a mixture of Li₂O, La₂O₃, ZrO₂, Ta₂O₅, and MnO₂ was used instead of a mixture of Li₂O, La₂O₃, ZrO₂, Ta₂O₅, and RuO₂ as the precursor mixture. The prepared solid ionic conductor had a composition of Li 6.5 La3Zr 1.4 Ta 0.5 Mn 0.1 O 12 .
[0282] Example 6: Li 6.5 La3Zr 1.4 Ta 0.5 Sn 0.1 O 12 Preparation
[0283] The solid ionic conductor was prepared in the same manner as in Example 1, except that a mixture of Li₂O, La₂O₃, ZrO₂, Ta₂O₅, and SnO₂ was used instead of a mixture of Li₂O, La₂O₃, ZrO₂, Ta₂O₅, and RuO₂ as the precursor mixture. The prepared solid ionic conductor had a composition of Li 6.5 La3Zr 1.4 Ta 0.5 Sn 0.1 O 12 .
[0284] Example 7: Li7La3Zr 0.49 Ta 0.49 Hf 0.49 Sc 0.49 Ru 0.04 O 12 Preparation
[0285] The solid ionic conductor was prepared in the same manner as in Example 1, except that: instead of the mixture of Li₂O, La₂O₃, ZrO₂, Ta₂O₅, RuO₂, HfO₂, and Sc₂O₃ in stoichiometric proportions, a mixture of Li₂O, La₂O₃, ZrO₂, Ta₂O₅, and RuO₂ was used as the precursor mixture. The prepared solid ionic conductor had the composition Li₇La₃Zr 0.49 Ta 0.49 Hf 0.4 9Sc 0.49 Ru 0.04 O 12 .
[0286] Example 8: Li7La3Zr 0.475 Ta 0.475 Hf 0.475 Sc 0.475 Ru 0.1 O 12 Preparation
[0287] Solid ionic conductors were prepared in the same manner as in Example 7, except that the stoichiometric ratios of ZrO2, Ta2O5, RuO2, HfO2, and Sc2O3 were changed.
[0288] The prepared solid ionic conductor has the composition Li7La3Zr 0.475 Ta 0.475 Hf 0.475 Sc 0.475 Ru 0.1 O 12 .
[0289] Comparative Example 1: Li 6.5 La3Zr 1.5 Ta 0.5 O 12 Preparation
[0290] The solid ionic conductor was prepared in the same manner as in Example 1, except that a mixture of Li₂O, La₂O₃, ZrO₂, and Ta₂O₅ was used instead of a mixture of Li₂O, La₂O₃, ZrO₂, Ta₂O₅, and RuO₂ as the precursor mixture. The prepared solid ionic conductor had a composition of Li 6.5 La3Zr 1.5 Ta 0.5 O 12 .
[0291] Comparative Example 2: Li7La3Zr 0.5 Hf 0.5 Sn 0.5 Ru 0.5 O 12 Preparation
[0292] Solid ionic conductors were prepared in the same manner as in Example 1, except that: as a precursor mixture, a mixture of Li2O, La2O3, ZrO2, HfO2, SnO2, and RuO2 combined in stoichiometric ratios was used instead of a mixture of Li2O, La2O3, ZrO2, Ta2O5, and RuO2.
[0293] The prepared solid ionic conductor has the composition Li7La3Zr 0.5 Hf 0.5 Sn 0.5 Ru 0.5 O 12 .
[0294] Manufacturing of all-solid-state secondary batteries
[0295] Example 9
[0296] Preparation of solid electrolyte layer-negative electrode layer laminate
[0297] Prepare the solid ion conductor wafer obtained in Example 1. A copper (Cu) current collector with a thickness of 10 μm is disposed on one surface of the wafer, and a foil with a thickness of 20 μm and deposited with lithium is disposed on one surface of the copper (Cu) current collector. A pressure of 250 MPa is applied to the wafer at 25°C by cold isostatic pressing (CIP) to assist the lithium electrode and the negative current collector in attaching them to the solid ion conductor wafer to prepare a solid electrolyte layer-lithium layer-negative current collector laminate.
[0298] Preparation of positive electrode layer
[0299] Preparing LiNi 0.8 Co 0.15 Mn 0.05 O2 (NCM) was used as the positive electrode active material. Additionally, polytetrafluoroethylene (Teflon, manufactured by DuPont Corporation, a registered trademark) was prepared as a binder. Furthermore, carbon nanofibers (CNF) were prepared as a conductive additive. These materials were then mixed at a weight ratio of positive electrode active material: conductive additive: binder = 100:2:1. The mixture was stretched into a sheet to prepare a positive electrode active material sheet. This positive electrode active material sheet was then pressed onto a positive electrode current collector made of aluminum foil with a thickness of 18 μm to prepare the positive electrode layer.
[0300] The prepared positive electrode active material layer was immersed in it, and 2.0M LiFSI (lithium bis(fluorosulfonyl)imide) was dissolved in the ionic liquid Pyr13FSI (bis(fluorosulfonyl)imide N-propyl-N-methyl-pyrrolidine). In the electrolyte solution.
[0301] Manufacturing of all-solid-state secondary batteries
[0302] The positive electrode layer is disposed within an SUS cap with the positive electrode active material layer immersed in the ionic liquid electrolyte facing upwards. A solid electrolyte layer-negative electrode layer stack is disposed on the positive electrode active material layer, such that the positive electrode active material layer and the solid electrolyte layer are in contact with each other, and then sealed to prepare an all-solid-state secondary battery. The negative electrode layer and the positive electrode layer are insulated with an insulator. A portion of the positive electrode current collector and a portion of the negative electrode current collector protrude outside the sealed battery and serve as positive electrode layer terminals and negative electrode layer terminals, respectively.
[0303] Examples 10-16
[0304] The all-solid-state secondary battery was manufactured in the same manner as in Example 9, except that the solid ion conductor wafers prepared in Examples 2-8 were used.
[0305] Comparative Examples 3 and 4
[0306] The all-solid-state secondary battery was manufactured in the same manner as in Example 9, except that the solid ion conductor wafers prepared in Comparative Examples 1 and 2 were used.
[0307] Evaluation Example 1: X-ray Diffraction Analysis
[0308] XRD spectra of the solid ionic conductor powders prepared in Examples 1-8 and Comparative Example 1 were measured, and some of the results are shown in... Figure 1 In this study, Cu Kα radiation was used for XRD analysis.
[0309] like Figure 1 As shown, the solid ionic conductors of Examples 1, 2, and Comparative Example 1 were found to have the same crystal structure. That is, in Examples 1 and 2, no change was found in the crystal structure regardless of the Ru substitution.
[0310] The solid ionic conductors of Examples 1, 2, and 1 were found to each have a garnet-like structure including a cubic phase, as they exhibit a single peak in the region where the diffraction angle 2θ is 16° to 17.5°.
[0311] Evaluation Example 2: Ionic Conductivity Measurement
[0312] The discs prepared in Examples 1-8 and Comparative Examples 1-2 were mirror-polished sequentially using 1200 / 2000 / 4000 / 7000 grit sandpaper. Subsequently, an Au layer with an 8 mm diameter was deposited on both surfaces of the discs by sputtering using a sputtering device to form Au electrodes, thereby preparing a structure consisting of an Au electrode / solid ion conductor disc / Au electrode.
[0313] In the structure consisting of an Au electrode / solid ion conductor disc / Au electrode, analysis using electrochemical impedance spectroscopy (EIS) is performed by connecting wires to the two surfaces of the Au electrode. EIS analysis is performed at an amplitude of approximately 10 mV and a frequency range of 0.1 Hz to 10 mV. 6 The impedance of the disc was measured at a frequency of Hz. A potentiostat / galvanostat and a 1455 Frequency Response Analyzer (FRA) multichannel test module (Solatron Analytical, UK) were used as the impedance analyzer, employing a two-probe method at room temperature (25°C). The impedance was measured in a dry chamber with a dew point of -60°C or less. The resistance values were obtained from the arcs of the Nyquist plot of the impedance measurements, and the area of the electrode region and the thickness of the disc were corrected for these resistance values to calculate the ionic conductivity, the results of which are shown in Table 1.
[0314] Furthermore, the ionic conductivity was measured according to temperature by changing the temperature of the chamber containing the disc during impedance measurements. The change in ionic conductivity according to temperature was converted into the Arrhenius plot shown, and the activation energy was calculated from the slope of the Arrhenius plot according to the Arrhenius equation expressed by Equation 1. Some of the results are shown in Table 1 and Figure 2 middle.
[0315] Equation 1
[0316] σ=Aexp(-Ea / kT)
[0317] In Equation 1, σ is the conductivity, A is the frequency factor, Ea is the activation energy, k is the Boltzmann constant, and T is the absolute temperature.
[0318] Table 1
[0319]
[0320] As shown in Table 1, the solid ionic conductors of Examples 1-2 exhibit a strength of 3 × 10⁻⁶ at room temperature. -4 S / cm or higher conductivity. The solid ionic conductors of Examples 1-2 exhibit ionic conductivity similar to that of Comparative Example 1.
[0321] The solid ionic conductors of Examples 1-2 exhibit low activation energies of 0.4 eV or less at room temperature.
[0322] Evaluation Example 3: Raman Spectroscopy Measurement
[0323] For the solid ion conductors prepared in Examples 1-5 and Comparative Example 1, after being placed in air for 24 hours immediately following their preparation, an image was obtained at 50 cm⁻¹ using a 514 nm laser source with approximately 1 mW power from Reinshaw Corporation's inVis device. -1 Up to 1400cm -1 Raman spectra within the range of .
[0324] The measurement results of the solid ionic conductors in Example 1 and Comparative Example 1 are shown in the figures below. Figure 3A and 3B middle.
[0325] like Figure 3A As shown, the solid ionic conductor of Example 1 has a capacitance of 600-800 cm⁻¹. -1 A strong peak is observed at this point. This peak is interpreted as being caused by bond stretching of the Ru-O bond. Therefore, it is determined that Ru-O bonds exist locally at a high concentration on the surface of the solid ionic conductor.
[0326] Despite Figure 3B The diagram also shows numerous peaks in the solid ionic conductor of Comparative Example 1, but... Figure 3B The intensity of the peak in Figure 3A In the 600cm -1 -800cm -1 The peaks at that location are significantly lower than those at other locations.
[0327] Evaluation Example 4: Interface Resistance Measurement
[0328] A lithium foil with a thickness of 20 μm was placed on one surface of each of the solid ionic conductor discs prepared in Examples 1-8 and Comparative Example 1, and a pressure of 250 MPa was applied to it at 25 °C by cold isostatic pressing (CIP) to attach the lithium electrode.
[0329] Lithium electrodes were attached to opposite surfaces of a wafer in the same manner to fabricate a lithium / solid electrolyte / lithium symmetric cell. Current collectors were disposed on the lithium electrodes on both surfaces of the wafer, and a portion of the current collectors was allowed to protrude beyond the sealed symmetric cell to serve as electrode terminals during sealing. The interfacial resistance of the wafer was measured using the fabricated symmetric cell.
[0330] The impedance of a symmetrical single-cell battery was measured using a potentiostat / galvanostat and a 1455 Frequency Response Analyzer (FRA) multichannel test module (Solatron Analytical, UK) as an impedance analyzer via the two-probe method. The impedance was measured at 25°C with an amplitude of 10mV and a frequency response range of 0.1Hz to 10mV. 6 The experiment was conducted in a dry chamber atmosphere with a frequency range of Hz and a dew point of -60 degrees Celsius.
[0331] The interface resistance is measured by the size of the arc in the Nyquist plot of the impedance measurement results, and some of the results are shown in Table 2.
[0332] Table 2
[0333] Example 1 27 Example 3 14 Example 5 34 Example 6 40 Comparative Example 1 89 Comparative Example 2 1970
[0334] As shown in Table 2, the interface resistance of the solid ionic conductors in Examples 1, 3, 5, and 6 is significantly reduced compared to the solid ionic conductors in Comparative Examples 1 and 2.
[0335] Compared to the solid ionic conductor of Comparative Example 1, in which the electrochemically active metal was not substituted, and the solid ionic conductor of Comparative Example 2, in which an excess of the electrochemically active metal was substituted, the solid ionic conductor of the embodiment in which a small amount of the electrochemically active metal was substituted at the Zr site showed a significant decrease in interfacial resistance. The high interfacial resistance of Comparative Example 2 was determined to be due to insulating byproducts at the interface caused by side reactions of lithium and the excess substituted metal.
[0336] Furthermore, in the solid ionic conductors of the embodiments, even 10 hours after the initial measurement point following the fabrication of the symmetrical cell, the interface resistance remained almost unchanged and remained constant. Therefore, it was found that the solid ionic conductors of the embodiments formed a stable interface for lithium metal. Conversely, in solid ionic conductors comprising an excess of electrochemically active metals, such as the solid ionic conductor of Comparative Example 2, the interface resistance increased over time and then converged to a constant value.
[0337] As observed in the Raman spectroscopy of Example 3, the high concentration of Ru-O bonds present on the surface of the solid ionic conductor of Example 1 was determined to act as a catalyst for the electrode reaction at the interface or to increase the affinity between the solid ionic conductor and Li, thereby reducing the interfacial resistance. The total resistance of the solid electrolyte layer consists of the interfacial resistance and the bulk resistance of the solid electrolyte layer. When the thickness of the solid electrolyte layer including the solid ionic conductor decreases, the portion of the total resistance due to the interfacial resistance of the solid ionic conductor increases compared to the portion due to the bulk resistance of the solid ionic conductor. Thus, when the solid ionic conductor forms a thin-film type solid electrolyte layer, the total resistance of the solid electrolyte layer mainly depends on the interfacial resistance of the solid ionic conductor. Therefore, the battery using a thin-film type solid ionic conductor with low interfacial resistance as the solid electrolyte layer exhibits significantly reduced internal resistance, improved reversibility of electrode reactions in the battery, and improved cycle characteristics.
[0338] Evaluation Example 5: Charge-Discharge Test
[0339] The charging and discharging characteristics of the all-solid-state secondary batteries manufactured in Examples 9-16 and Comparative Examples 3-4 were evaluated by the following charge-discharge tests. The charge-discharge tests were performed by placing the all-solid-state secondary batteries in a thermostat at 60°C.
[0340] In the first cycle, the secondary battery was charged at 0.2 mA / cm. 2 The battery was charged with a constant current until the voltage reached 4.3V. Then, the secondary battery was charged at 0.2mA / cm². 2 Discharge at a constant current until the battery voltage reaches 2.85V.
[0341] In the second cycle, the secondary battery was charged at 0.4 mA / cm². 2 The battery was charged with a constant current until the voltage reached 4.3V. Then, the secondary battery was charged at 0.4mA / cm². 2 Discharge at a constant current until the battery voltage reaches 2.85V.
[0342] In the third cycle, the secondary battery was charged at 0.6 mA / cm. 2 The battery was charged with a constant current until the voltage reached 4.3V. Then, the secondary battery was charged at 0.6mA / cm². 2 Discharge at a constant current until the battery voltage reaches 2.85V.
[0343] In the fourth cycle, the secondary battery was charged at 0.8 mA / cm. 2 The battery was charged with a constant current until the voltage reached 4.3V. Then, the secondary battery was charged at 0.8mA / cm². 2Discharge at a constant current until the battery voltage reaches 2.85V.
[0344] In the fifth cycle, the secondary battery was charged at 1.0 mA / cm². 2 The battery was charged with a constant current until the voltage reached 4.3V. Then, the secondary battery was charged at 1.0mA / cm². 2 Discharge at a constant current until the battery voltage reaches 2.85V.
[0345] In the sixth cycle, the secondary battery was charged at 1.2 mA / cm². 2 The battery was charged with a constant current until the voltage reached 4.3V. Then, the secondary battery was charged at 1.2mA / cm². 2 Discharge at a constant current until the battery voltage reaches 2.85V.
[0346] Figure 4 The charge-discharge curves of the all-solid-state secondary battery of Example 9 are shown. Figure 4 In this context, ΔJ represents the difference in charging / discharging current between cycles.
[0347] like Figure 4 As shown, it performs stable charging and discharging across the entire current range.
[0348] According to one aspect of the implementation, the solid ionic conductor, comprising a novel composition of garnet-type oxide, provides excellent ionic conductivity and reduced interfacial resistance to lithium metal, thereby allowing the electrochemical device comprising the solid ionic conductor to provide excellent charge-discharge characteristics.
[0349] It should be understood that the embodiments described herein are to be considered in the descriptive sense only and are not intended for limiting purposes. The descriptions of features or aspects in each embodiment should typically be considered applicable to other similar features or aspects in other embodiments. Although one or more embodiments have been described with reference to the accompanying drawings, those skilled in the art will understand that various changes in form and detail may be made therein without departing from the spirit and scope defined by the appended claims.
Claims
1. Solid ionic conductors, including: The garnet-type oxide represented by Formula 2: Formula 2 Li A M1 B (La a1 M2 a2 3(Zr b1 M3 b2 M4 b3 2O H X I wherein, in Formula 2, M1 is a monovalent cation, a divalent cation, a trivalent cation, or a combination thereof, M2 is a monovalent cation, a divalent cation, a trivalent cation, or a combination thereof, M3 is Al, Ga, Ta, Nb, Hf, Ti, V, Cr, Co, Ni, Cu, Mo, W, Mg, Tc, Pd, Sc, Cd, In, Sb, Te, Tl, Pt, Si, or a combination thereof, M4 is Ir, Ru, Mn, Sn, or a combination thereof, X is a monovalent anion, a divalent anion, a trivalent anion, or a combination thereof, 6≤A≤8, 0≤B<2, 9≤H≤12, and 0≤I≤2 are satisfied, and a1+a2=1, 0<a1≤1, 0≤a2≤0.067, b1+b2+b3=1, 0<b1<1, 0<b2<1, and 0<b3≤0.1 are satisfied.
2. The solid ion conductor according to claim 1, wherein the garnet-type oxide represented by Formula 2 is a garnet-type oxide represented by Formula 3: Formula 3 Li A M1 B (La a1 M2 a2 3(Zr b1 M5 b4 M6 b5 M7 b6 M8 b7 2O H X I in, in Formula 3, M1 is a monovalent cation, a divalent cation, a trivalent cation, or a combination thereof, M2 is a monovalent cation, a divalent cation, a trivalent cation, or a combination thereof, M5, M6, and M7 are each independently Al, Ga, Ta, Nb, Hf, Ti, V, Cr, Co, Ni, Cu, Mo, W, Mg, Tc, Pd, Sc, Cd, In, Sb, Te, Tl, Pt, Si, or a combination thereof, M8 is Ir, Ru, Mn, Sn, or a combination thereof, X is a monovalent anion, a divalent anion, a trivalent anion, or a combination thereof, 6≤A≤8, 0≤B<2, 9≤H≤12, and 0≤I≤2 are satisfied, and a1+a2=1, 0<a1≤1, 0≤a2≤0.067, b1+b4+b5+b6+b7=1, 0<b1<1, 0<b4<1, 0<b5<1, 0≤b6<1, and 0<b7≤0.1 are satisfied.
3. The solid ion conductor according to claim 1, wherein the garnet-type oxide represented by Formula 2 is a garnet-type oxide represented by Formula 4: Formula 4 The 7-w M1 x The 3-y M2 y Zr 2-z-u M3 z M4 u O 12-v X v in, in Formula 4, M1 is H, Fe, Ga, Al, B, Be, or a combination thereof, M2 is Ba, Ca, Sr, Y, Bi, Pr, Nd, Ac, Sm, Gd, or a combination thereof, M3 is Al, Ga, Ta, Nb, Hf, Ti, V, Cr, Co, Ni, Cu, Mo, W, Mg, Tc, Pd, Sc, Cd, In, Sb, Te, Tl, Pt, Si, or a combination thereof, M4 is Ir, Ru, Mn, Sn, or a combination thereof, X is a monovalent anion, a divalent anion, a trivalent anion, or a combination thereof, 0≤x≤2, 0≤y≤0.2, 0<z<2, 0<u≤0.2, 0<v<2, 0<z+u<2, and w=[a×x]+[(b-3)×y]+[(c-4)×z]+[(d-4)×u]+[(e+2)×v] are satisfied, and a is the oxidation number of M1, b is the oxidation number of M2, c is the oxidation number of M3, d is the oxidation number of M4, and e is the oxidation number of X.
4. The solid ionic conductor as claimed in claim 1, wherein the garnet-type oxide represented by Formula 2 is a garnet-type oxide represented by Formula 5: Formula 5 Li 7-w M1 x La 3-y M2 y Zr 2-p-q-r-s M5 p M6 q M7 r M8 s O 12-v X v in, In Formula 5, M1 is H, Fe, Ga, Al, B, Be, or a combination thereof, M2 is Ba, Ca, Sr, Y, Bi, Pr, Nd, Ac, Sm, Gd, or a combination thereof, M5, M6, and M7 are each independently Al, Ga, Ta, Nb, Hf, Ti, V, Cr, Co, Ni, Cu, Mo, W, Mg, Tc, Pd, Sc, Cd, In, Sb, Te, Tl, Pt, Si, or a combination thereof, M8 is Ir, Ru, Mn, Sn, or a combination thereof, X is a monovalent anion, a divalent anion, a trivalent anion, or a combination thereof, 0≤x≤2, 0≤y≤0.2, 0<p<2, 0<q<2, 0≤r<2, 0<s≤0.2, 0<v<2, 0<p+q+r+s<2, and w=[a×x]+[(b-3)×y]+[(f-4)×p]+[(g-4)×q]+[(h-4)×r]+[(i-4)×s]+[(e+2)×v] are satisfied, and a is the oxidation number of M1, b is the oxidation number of M2, f is the oxidation number of M5, g is the oxidation number of M6, h is the oxidation number of M7, i is the oxidation number of M8, and e is the oxidation number of X.
5. The solid ionic conductor as described in claim 1, wherein, In Formula 2, X is iodine, chlorine, bromine, fluorine, cyanide, cyanate, thiocyanate, azide, or a combination thereof.
6. The solid ionic conductor as claimed in claim 1, wherein the garnet-type oxide represented by Formula 2 is a garnet-type oxide represented by Formula 6: Formula 6 Li 7-w La3Zr 2-z-u M9 z M10 u O 12 in, In Formula 6, M9 is Al, Ga, Ta, Nb, Hf, Ti, V, Cr, Co, Ni, Cu, Mo, W, Mg, Tc, Pd, Sc, Cd, In, Sb, Te, Tl, Pt, Si, or a combination thereof, M10 is Ir, Ru, Mn, Sn, or a combination thereof, c is the oxidation number of M9, and d is the oxidation number of M10, and 0<z<2, 0<u≤0.2, 0<z+u<2, and w=[(c-4)×z]+[(d-4)×u] are satisfied.
7. The solid ionic conductor as claimed in claim 6, wherein M9 is Al, Ga, Ta, Nb, or a combination thereof, and M10 is Ir, Ru, or a combination thereof.
8. The solid ionic conductor as claimed in claim 1, wherein the garnet-type oxide represented by Formula 2 is a garnet-type oxide represented by Formula 7: Formula 7 Li 7-w La3Zr 2-p-q-r-s M11 p M12 q M13 r M14 s O 12 in, In Formula 7, M11, M12, and M13 are each independently Al, Ga, Ta, Nb, Hf, Ti, V, Cr, Co, Ni, Cu, Mo, W, Mg, Tc, Pd, Sc, Cd, In, Sb, Te, Tl, Pt, Si, or a combination thereof, M14 is Ir, Ru, Mn, Sn, or a combination thereof, f is the oxidation number of M11, g is the oxidation number of M12, h is the oxidation number of M13, and i is the oxidation number of M14, and satisfy 0<p<2, 0<q<2, 0≤r<2, 0<s≤0.2, 0<p+q+r+s<2, and w=[(f-4)×p]+[(g-4)×q]+[(h-4)×r]+[(i-4)×s].
9. The solid ionic conductor according to claim 8, wherein M11 is Al, Ga, Ta, Nb, or a combination thereof, M12 and M13 are each independently Hf, Sc, In, or a combination thereof, and M14 is Ir, Ru, Sn, or a combination thereof.
10. The solid ionic conductor according to claim 1, wherein the garnet-type oxide represented by Formula 2 is a garnet-type oxide represented by any one of the following formulas: Wherein 6≤7-w≤8, 0<z≤1, and 0<u≤0.2, Li 7-w La3Zr 2-z-u Al z Ir u O 12 , wherein 6≤7-w≤8, 0<z≤1, and 0<u≤0.2, Li 7-w La3Zr 2-z-u Al z Ru u O 12 , wherein 6≤7-w≤8, 0<z≤1, and 0<u≤0.2, Li 7- w La3Zr 2-z-u Al z Mn u O 12 , wherein 6≤7-w≤8, 0<z≤1, and 0<u≤0.2, Li 7-w La3Zr 2-z-u Al z Sn u O 12 ; where 6≤7-w≤8, 0<z≤1, and 0<u≤0.2, Li 7-w La3Zr 2-z-u Ga z Ir u O 12 , where 6≤7-w≤8, 0<z≤1, and 0<u≤0.2, Li 7-w La3Zr 2-z-u Ga z Ru u O 12 , where 6≤7-w≤8, 0<z≤1, and 0<u≤0.2, Li 7- w La3Zr 2-z-u Ga z Mn u O 12 , where 6≤7-w≤8, 0<z≤1, and 0<u≤0.2, Li 7-w La3Zr 2-z-u Ga z Sn u O 12 ; Wherein 6≤7-w≤8, 0<z≤1, and 0<u≤0.2, Li 7-w La3Zr 2-z-u Ta z Ir u O 12 , wherein 6≤7-w≤8, 0<z≤1, and 0<u≤0.2, Li 7-w La3Zr 2-z-u Ta z Ru u O 12 , wherein 6≤7-w≤8, 0<z≤1, and 0<u≤0.2, Li 7- w La3Zr 2-z-u Ta z Mn u O 12 , wherein 6≤7-w≤8, 0<z≤1, and 0<u≤0.2, Li 7-w La3Zr 2-z-u Ta z Sn u O 12 ; Li where 6≤7-w≤8, 0<z≤1, and 0<u≤0.2 7-w La3Zr 2-z-u Nb z Ir u O 12 , Li where 6≤7-w≤8, 0<z≤1, and 0<u≤0.2 7-w La3Zr 2-z-u Nb z Ru u O 12 , Li where 6≤7-w≤8, 0<z≤1, and 0<u≤0.2 7- w La3Zr 2-z-u Nb z Mn u O 12 , Li where 6≤7-w≤8, 0<z≤1, and 0<u≤0.2 7-w La3Zr 2-z-u Nb z Sn u O 12 ; where 6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, and 0<p+q+r+s<2, Li 7-w La3Zr 2-p-q-r- s Al p Hf q Sc r Ir s O 12 , where 6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, and 0<p+q+r+s<2, Li 7-w La3Zr 2-p-q-r-s Al p Hf q Sc r Ru s O 12 , where 6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, and 0<p+q+r+s<2, Li 7-w La3Zr 2-p-q-r-s Al p Hf q Sc r Mn s O 12 , where 6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, and 0<p+q+r+s<2, Li 7-w La3Zr 2-p-q-r-s Al p Hf q Sc r Sn s O 12 ; where 6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, and 0<p+q+r+s<2, Li 7-w La3Zr 2-p-q-r- s Ga p Hf q Sc r Ir s O 12 , where 6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, and 0<p+q+r+s<2, Li 7-w La3Zr 2-p-q-r-s Ga p Hf q Sc r Ru s O 12 , where 6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, and 0<p+q+r+s<2, Li 7-w La3Zr 2-p-q-r-s Ga p Hf q Sc r Mn s O 12 , where 6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, and 0<p+q+r+s<2, Li 7-w La3Zr 2-p-q-r-s Ga p Hf q Sc r Sn s O 12 ; where 6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, and 0<p+q+r+s<2, Li 7-w La3Zr 2-p-q-r- s Ta p Hf q Sc r Ir s O 12 , where 6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, and 0<p+q+r+s<2, Li 7-w La3Zr 2-p-q-r-s Ta p Hf q Sc r Ru s O 12 , where 6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, and 0<p+q+r+s<2, Li 7-w La3Zr 2-p-q-r-s Ta p Hf q Sc r Mn s O 12 , where 6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, and 0<p+q+r+s<2, Li 7-w La3Zr 2-p-q-r-s Ta p Hf q Sc r Sn s O 12 ; where 6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, and 0<p+q+r+s<2, Li 7-w La3Zr 2-p-q-r- s Nb p Hf q Sc r Ir s O 12 , where 6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, and 0<p+q+r+s<2, Li 7-w La3Zr 2-p-q-r-s Nb p Hf q Sc r Ru s O 12 , where 6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, and 0<p+q+r+s<2, Li 7-w La3Zr 2-p-q-r-s Nb p Hf q Sc r Mn s O 12 , or where 6≤7-w≤8, 0<p≤1, 0<q≤1, 0<r≤1, 0<s≤0.2, and 0<p+q+r+s<2, Li 7-w La3Zr 2-p-q-r-s Nb p Hf q Sc r Sn s O 12 .
11. The solid ionic conductor according to claim 1, wherein the garnet-type oxide represented by Formula 2 is a garnet-type oxide represented by any one of the following formulas: Li 7.5 La3Zr 1.4 Al 0.5 Ir 0.1 O 12 Li 7.5 La3Zr 1.3 Al 0.5 Ir 0.2 O 12 Li 7.5 La3Zr 1.4 Ga 0.5 Ir 0.1 O 12 Li 7.5 La3Zr 1.3 Ga 0.5 Ir 0.2 O 12 Li 6.5 La3Zr 1.4 Ta 0.5 Ir 0.1 O 12 Li 6.5 La3Zr 1.3 Ta 0.5 Ir 0.2 O 12 Li 6.5 La3Zr 1.4 Nb 0.5 Ir 0.1 O 12 Li 6.5 La3Zr 1.3 Nb 0.5 Ir 0.2 O 12 ; Li 7.5 La3Zr 1.4 Al 0.5 Ru 0.1 O 12 Li 7.5 La3Zr 1.3 Al 0.5 Ru 0.2 O 12 Li 7.5 La3Zr 1.4 Ga 0.5 Ru 0.1 O 12 Li 7.5 La3Zr 1.3 Ga 0.5 Ru 0.2 O 12 Li 6.5 La3Zr 1.4 Ta 0.5 Ru 0.1 O 12 Li 6.5 La3Zr 1.3 Ta 0.5 Ru 0.2 O 12 Li 6.5 La3Zr 1.4 Nb 0.5 Ru 0.1 O 12 Li 6.5 La3Zr 1.3 Nb 0.5 Ru 0.2 O 12 ; Li 7.5 La3Zr 1.4 Al 0.5 Mn 0.1 O 12 Li 7.5 La3Zr 1.3 Al 0.5 Mn 0.2 O 12 Li 7.5 La3Zr 1.4 Ga 0.5 Mn 0.1 O 12 Li 7.5 La3Zr 1.3 Ga 0.5 Mn 0.2 O 12 Li 6.5 La3Zr 1.4 Ta 0.5 Mn 0.1 O 12 Li 6.5 La3Zr 1.3 Ta 0.5 Mn 0.2 O 12 Li 6.5 La3Zr 1.4 Nb 0.5 Mn 0.1 O 12 Li 6.5 La3Zr 1.3 Nb 0.5 Mn 0.2 O 12 ; Li 7.5 La3Zr 1.4 Al 0.5 Sn 0.1 O 12 Li 7.5 La3Zr 1.3 Al 0.5 Sn 0.2 O 12 Li 7.5 La3Zr 1.4 Ga 0.5 Sn 0.1 O 12 Li 7.5 La3Zr 1.3 Ga 0.5 Sn 0.2 O 12 Li 6.5 La3Zr 1.4 Ta 0.5 Sn 0.1 O 12 Li 6.5 La3Zr 1.3 Ta 0.5 Sn 0.2 O 12 Li 6.5 La3Zr 1.4 Nb 0.5 Sn 0.1 O 12 Li 6.5 La3Zr 1.3 Nb 0.5 Sn 0.2 O 12 ; Li 7.98 La3Zr 0.49 Al 0.49 Hf 0.49 Sc 0.49 Ir 0.04 O 12 Li 7.95 La3Zr 0.475 Al 0.475 Hf 0.475 Sc 0.475 Ir 0.1 O 12 Li 7.98 La3Zr 0.49 Ga 0.49 Hf 0.49 Sc 0.49 Ir 0.04 O 12 Li 7.95 La3Zr 0.475 Ga 0.475 Hf 0.475 Sc 0.475 Ir 0.1 O 12 Li7La3Zr 0.49 Ta 0.49 Hf 0.49 Sc 0.49 Ir 0.04 O 12 Li7La3Zr 0.475 Ta 0.475 Hf 0.475 Sc 0.475 Ir 0.1 O 12 Li7La3Zr 0.49 Nb 0.49 Hf 0.49 Sc 0.49 Ir 0.04 O 12 Li7La3Zr 0.475 Nb 0.475 Hf 0.475 Sc 0.475 Ir 0.1 O 12 ; Li 7.98 La3Zr 0.49 Al 0.49 Hf 0.49 Sc 0.49 Ru 0.04 O 12 Li 7.95 La3Zr 0.475 Al 0.475 Hf 0.475 Sc 0.475 Ru 0.1 O 12 Li 7.98 La3Zr 0.49 Ga 0.49 Hf 0.49 Sc 0.49 Ru 0.04 O 12 Li 7.95 La3Zr 0.475 Ga 0.475 Hf 0.475 Sc 0.475 Ru 0.1 O 12 Li7La3Zr 0.49 Ta 0.49 Hf 0.49 Sc 0.49 Ru 0.04 O 12 Li7La3Zr 0.475 Ta 0.475 Hf 0.475 Sc 0.475 Ru 0.1 O 12 Li7La3Zr 0.49 Nb 0.49 Hf 0.49 Sc 0.49 Ru 0.04 O 12 Li7La3Zr 0.475 Nb 0.475 Hf 0.475 Sc 0.475 Ru 0.1 O 12 ; Li 7.98 La3Zr 0.49 Al 0.49 Hf 0.49 Sc 0.49 Mn 0.04 O 12 Li 7.95 La3Zr 0.475 Al 0.475 Hf 0.475 Sc 0.475 Mn 0.1 O 12 Li 7.98 La3Zr 0.49 Ga 0.49 Hf 0.49 Sc 0.49 Mn 0.04 O 12 Li 7.95 La3Zr 0.475 Ga 0.475 Hf 0.475 Sc 0.475 Mn 0.1 O 12 Li7La3Zr 0.49 Ta 0.49 Hf 0.49 Sc 0.49 Mn 0.04 O 12 Li7La3Zr 0.475 Ta 0.475 Hf 0.475 Sc 0.475 Mn 0.1 O 12 Li7La3Zr 0.49 Nb 0.49 Hf 0.49 Sc 0.49 Mn 0.04 O 12 Li7La3Zr 0.475 Nb 0.475 Hf 0.475 Sc 0.475 Mn 0.1 O 12 ; Li 7.98 La3Zr 0.49 Al 0.49 Hf 0.49 Sc 0.49 Sn 0.04 O 12 , Li 7.95 La3Zr 0.475 Al 0.475 Hf 0.475 Sc 0.475 Sn 0.1 O 12 , Li 7.98 La3Zr 0.49 Ga 0.49 Hf 0.49 Sc 0.49 Sn 0.04 O 12 , Li 7.95 La3Zr 0.475 Ga 0.475 Hf 0.475 Sc 0.475 Sn 0.1 O 12 , Li7La3Zr 0.49 Ta 0.49 Hf 0.49 Sc 0.49 Sn 0.04 O 12 , Li7La3Zr 0.475 Ta 0.475 Hf 0.475 Sc 0.475 Sn 0.1 O 12 , Li7La3Zr 0.49 Nb 0.49 Hf 0.49 Sc 0.49 Sn 0.04 O 12 , or Li7La3Zr 0.475 Nb 0.475 Hf 0.475 Sc 0.475 Sn 0.1 O 12 .
12. The solid ionic conductor according to claim 1, wherein the garnet-type oxide comprises a cubic phase.
13. The solid ion conductor of claim 1, wherein the lithium-ion conductivity of the solid ion conductor is 1.0 × 10⁻⁶. -4 S / cm up to 1.0×10 -3 S / cm.
14. The solid ionic conductor according to claim 1, wherein the solid ionic conductor has an activation energy of 0.3 eV to 0.4 eV in a temperature range of 25 °C to 100 °C.
15. The solid ionic conductor of claim 1, wherein the solid ionic conductor exhibits a Raman spectrum at 600 cm⁻¹ -1 Up to 800 cm -1 It has a peak.
16. The solid ionic conductor of claim 1, wherein when passed at a temperature of 25 °C at 0.1 Hz to 10 Hz... 6 When measuring the impedance spectroscopy of a lithium-symmetric cell with electrodes positioned between lithium metal electrodes within a frequency range of Hz, the interfacial resistance between the solid ionic conductor and the lithium metal is 1 Ω·cm. 2 Up to 60 Ω·cm 2 .
17. A solid electrolyte, comprising the solid ionic conductor according to any one of claims 1 to 16.
18. An electrochemical device, comprising: a positive electrode; a negative electrode; and a solid electrolyte layer disposed between the positive electrode and the negative electrode, wherein the positive electrode, the negative electrode, the solid electrolyte layer, or a combination thereof comprises the solid ionic conductor according to any one of claims 1 to 16.
19. The electrochemical device according to claim 18, further comprising a positive electrode protective layer, a negative electrode protective layer, a solid electrolyte protective layer, or a combination thereof.
20. The electrochemical device according to claim 18, wherein the electrochemical device is an all-solid secondary battery or a metal-air battery.
21. A method for preparing the solid ionic conductor according to any one of claims 1 to 16, the method comprising: providing a precursor mixture comprising a precursor for forming the solid ionic conductor; and subjecting the precursor mixture to heat treatment in an oxidizing atmosphere to provide the solid ionic conductor.
22. The method according to claim 21, wherein the heat treatment of the precursor mixture comprises heat treating at 600 °C to 1100 °C.
23. The method according to claim 21, further comprising: molding the solid ionic conductor to prepare a molded product; and subjecting the molded product to heat treatment at 900 °C to 1500 °C to prepare a sintered product, wherein the molded product is heat treated at a higher temperature than the precursor mixture.
Citation Information
Patent Citations
Hotfix magnet
KR1020200098821A
Anion-doped ion conductor material as well as preparation method and application thereof
CN111370755A